Light Control Film
By designing a light control film with alternating transmission and absorption areas, and adopting a microstructured film and layer-by-layer self-assembly process, the problem of insufficient axial transmittance and viewing angle dependence in private film applications is solved. Achieve efficient light control effect.
Patent Information
- Application Number
- CN201980082268.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-12-11
- Filing Date
- 2019-12-02
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2039-12-02
AI Technical Summary
It is difficult for existing light control films to achieve excellent axial transmittance and viewing angle-dependent light transmission characteristics in private film applications.
A light control film is designed, which includes alternate transmission areas and absorption areas, with an aspect ratio, and an absorption layer or a reflection layer is provided between the light input surface and the light output surface. The light control film is prepared by a microstructured film and a layer-by-layer self-assembly process to ensure the aspect ratio and optical characteristics of the absorbed area.
A high relative transmittance at a 0-degree viewing angle is achieved, while significantly reducing the transmittance at an off-axis viewing angle, meeting the needs of a private film.
Smart Images

Figure CN113490867B_ABST
Abstract
Description
Summary of the invention
[0001] While various light management films have been described, the industry would recognize the advantages of a light management film suitable for use as a privacy film having improved properties, such as improved on-axis transmission.
[0002] In one embodiment, a light control film is described, which includes: a light input surface and a light output surface opposite to the light input surface; alternating transmission regions and absorption regions, which are arranged between the light input surface and the light output surface, wherein the absorption region has an aspect ratio of at least 30; and an absorption layer or a reflective layer, which is arranged between the alternating transmission regions and absorption regions and the light input surface and / or the light output surface, provided that the reflective layer is not a wavelength shifting film.
[0003] The absorbing layer typically includes pigments and / or dyes.
[0004] In some embodiments, the absorptive layer includes an adhesive or coating disposed between the alternating transmissive and absorptive regions and the light output surface or the light input surface.
[0005] In other embodiments, the absorptive layer comprises a (eg, preformed) film layer disposed between the alternating transmissive and absorptive regions and the light input surface or the light output surface. The film layer may be a cover film or a substrate layer.
[0006] In another embodiment, a light control film is described, which includes a light input surface and a light output surface opposite to the light input surface; and alternating transmissive regions and absorptive regions, which are arranged between the light input surface and the light output surface, wherein the absorptive regions have an aspect ratio of at least 30 and the alternating transmissive regions include an absorptive material.
[0007] The light absorbing material of the transmissive region typically comprises a pigment and / or a dye.
[0008] Also described is a light detection system comprising:
[0009] A light source configured to emit light having a first spectral distribution along a first direction and a second spectral distribution along a different second direction; a detector sensitive to wavelengths within a detection wavelength range; and a light control film as described herein disposed on the light source or the detector so as to receive and transmit light emitted by the light source. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1a is a cross-sectional view of a light control film according to a specific embodiment.
[0011] Figure 1bShow Figure 1a The polar cut-off viewing angle of the light control film.
[0012] Figure 1c is a perspective view of a comparative microstructured film.
[0013] Figure 2 is a perspective view of a microstructured film.
[0014] Figure 3 The cross-sectional schematic diagram is a specific embodiment of the method for preparing the light control film.
[0015] Figure 4 is a perspective view of a light management film further comprising a cover film bonded to the adhesive layer.
[0016] Figure 5 is a perspective schematic diagram of a backlit display including an embodied light management film.
[0017] Figure 6 The graph is a graph of the brightness versus viewing angle of various light control films.
[0018] Figure 7 is a schematic cross-sectional view of an exemplary light control film applied to an enclosure such as a window of a building, a house, or a vehicle.
[0019] Figure 8 is a schematic graph of the transmittance of the light control film versus wavelength.
[0020] Fig. 9 Schematic diagram of an exemplary application of a light control film to an aircraft or aircraft.
[0021] Fig.10 is a schematic cross-sectional view of an exemplary optical communication system including a light control film in combination with a retroreflector.
[0022] Fig.11 is a schematic cross-sectional view of an exemplary wearable optical communication system including a light control film and a wristwatch with a pulse sensor.
[0023] Fig.12 is a graph of percent transmission versus wavelength. DETAILED DESCRIPTION
[0024] In one embodiment, a light control film ("LCF") is described. Figure 1a (a cross-sectional view of an embodied LCF 100), the LCF includes a light output surface 120 and an opposing light input surface 110. The light output surface 120 is generally parallel to the light input surface 110. The LCF 100 includes alternating transmissive regions 130 and absorptive regions 140 disposed between the light output surface 120 and the light input surface 110.
[0025] In one embodiment, if Figure 1a As shown, the transmissive regions 130 are generally integral with the land regions "L", meaning that there is no interface between the land regions and the base portion 131 of the transmissive regions 130. Alternatively, the LCF may be free of such land regions L, or there may be an interface between the land regions L and the transmissive regions 130. When land regions are present, they are disposed between the alternating transmissive regions 130 and absorptive regions 140 and the light input surface 110.
[0026] Alternatively, in another embodiment, surface 120 can be the light input surface and surface 110 can be the light output surface. In this embodiment, the matrix region is disposed between the alternating transmissive regions 130 and absorptive regions 140 and the light output surface.
[0027] The transmissive region 130 may have a width “W T " is defined. In addition to the base region "L", the transmissive region 130 generally has the same nominal height as the absorptive region 140. In a typical embodiment, the height H of the absorptive region A The height is at least 30 microns, 40 microns, 50 microns, 60 microns, 70 microns, 80 microns, 90 microns, or 100 microns. In some embodiments, the height is no greater than 200 microns, 190 microns, 180 microns, 170 microns, 160 microns, or 150 microns. In some embodiments, the height is no greater than 140 microns, 130 microns, 120 microns, 110 microns, or 100 microns. The LCF typically includes multiple transmissive regions with nominally the same height and width. In some embodiments, the transmissive region has a height "H T ”, the maximum width at its widest part “W T ” and an aspect ratio H of at least 1.75 T / W T In some embodiments, H T / W T In other embodiments, the aspect ratio of the transmissive region is at least 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, or 5.0. In other embodiments, the aspect ratio of the transmissive region is at least 6, 7, 8, 9, 10. In other embodiments, the aspect ratio of the transmissive region is at least 15, 20, 25, 30, 35, 40, 45, or 50.
[0028] The absorbent region 140 has a height “H” defined by the distance between the bottom surface 155 and the top surface 145. A Such top and bottom surfaces are generally parallel to the light output surface 120 and the light input surface 110. The absorption region 140 has a maximum width "W A ”, and are spaced apart at intervals “P” along the surface light output surface 120. A The absorption area also has Figure 5 The length "L A The width is typically the smallest dimension. The height is typically greater than the width. The length is typically the largest dimension. In some embodiments, the length may span the entire length of a sheet of film or span the length of an entire roll of film.
[0029] The width W of the absorption region at the base (ie, adjacent to the bottom surface 155) is A The absorption region is typically nominally the same as the width of the absorption region adjacent to the top surface 145. However, when the width of the absorption region at the base is different from the width adjacent to the top surface, the width is defined by the maximum width. The maximum widths of multiple absorption regions can be averaged for an area of interest, such as an area where transmittance (e.g., brightness) is measured. The LCF typically includes multiple absorption regions with nominally the same height and width. In typical embodiments, the absorption region typically has a width of no more than 10 microns, 9 microns, 8 microns, 7 microns, 6 microns, 5 microns, 4 microns, 3 microns, 2 microns, or 1 micron. In some embodiments, the absorption region typically has a width of no more than 900 nanometers, 800 nanometers, 700 nanometers, 600 nanometers, or 500 nanometers. In some embodiments, the absorption region has a width of at least 50 nanometers, 60 nanometers, 70 nanometers, 80 nanometers, 90 nanometers, or 100 nanometers.
[0030] The absorption region can be defined by the aspect ratio, that is, the height of the absorption region divided by the maximum width of the absorption region (H A / W A ). In some embodiments, the aspect ratio of the absorption region is at least 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10. In advantageous embodiments, the height and width of one or more absorption regions are selected so that one or more absorption regions have an even higher aspect ratio. In some embodiments, the aspect ratio of the absorption region is at least 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100. In other embodiments, the aspect ratio of the absorption region is at least 200, 300, 400, or 500. The aspect ratio can range up to 10,000 or more. In some embodiments, the aspect ratio is no greater than 9,000; 8,000 g / mol, 7,000 g / mol, 6,000; 5,000; 4,000; 3000; 2,000; or 1,000.
[0031] like Figure 1b As shown, LCF 100 includes alternating transmissive regions 130 and absorptive regions 140, and an interface 150 between the transmissive regions 130 and the absorptive regions 140. The interface 150 forms a wall angle θ with a line 160 perpendicular to the light output surface 120.
[0032] A larger wall angle θ reduces the transmittance at normal incidence or in other words at a viewing angle of 0 degrees. A smaller wall angle is preferred so that the transmittance at normal incidence can be as large as possible. In some embodiments, the wall angle θ is less than 10 degrees, 9 degrees, 8 degrees, 7 degrees, 6 degrees, or 5 degrees. In some embodiments, the wall angle is no greater than 2.5 degrees, 2.0 degrees, 1.5 degrees, 1.0 degrees, 0.5 degrees, or 0.1 degrees. In some embodiments, the wall angle is zero or close to zero. When the wall angle is zero, the angle between the absorption region and the light output surface 120 is 90 degrees. Depending on the wall angle, the transmission region may have a rectangular or trapezoidal cross-section.
[0033] When incident light undergoes total internal reflection (TIR) from the interface between the absorptive and transmissive regions, the transmittance (e.g., visible light brightness) can be increased. Whether the light will undergo TIR can be determined by the angle of incidence of the light with the interface and the difference in refractive index of the materials of the transmissive and absorptive regions.
[0034] like Figure 1b As shown, the transmissive regions 130 between the absorptive regions 140 have an interface angle θ defined by the geometry of the alternating transmissive regions 130 and absorptive regions. I .like Figure 1a and Figure 1b As shown, the interface angle θ I The first line extends from a first point defined by the bottom surface and side wall surface of the first absorbent region and a second point defined by the top surface and side wall surface of the nearest second absorbent region. The second line extends from a first point defined by the top surface and side wall surface of the first absorbent region and a second point defined by the bottom surface and side wall surface of the second absorbent region.
[0035] The polar cutoff viewing angle θP is equal to the sum of the polar cutoff half viewing angle θ1 and the polar cutoff half viewing angle θ2, each of which is measured from the normal to the light input surface 110. In a typical embodiment, the polar cutoff viewing angle θP is symmetrical, and the polar cutoff half viewing angle θ1 is equal to the polar cutoff half viewing angle θ2. Alternatively, the polar cutoff viewing angle θP can be asymmetrical, and the polar cutoff half viewing angle θ1 is not equal to the polar cutoff half viewing angle θ2.
[0036] Brightness can be measured according to the test method described in the examples. Figure 1a ) or a total light control film that may also include a cover film (such as Figure 4 Relative transmittance (e.g., visible light brightness) is defined as the percentage of light brightness at a specified viewing angle or viewing angle range between the reading with a light control film that includes alternating transmissive and absorptive regions and optionally other layers and the reading without the light control film (i.e., the baseline). Figure 6 The viewing angle may be in the range of -90 degrees to +90 degrees. The viewing angle of 0 degrees is perpendicular to the light input surface 110; while the viewing angles of -90 degrees and +90 degrees are parallel to the light input surface 110.
[0037] For example, refer to Figure 6 , axial baseline brightness is 2100Cd / m 2 Example 6 has 1910Cd / m 2 The relative transmittance (i.e., brightness) is therefore 1910 Cd / m 2 / 2100Cd / m 2 Multiplied by 100, this equals 91.0%. Unless otherwise indicated, relative transmittance refers to the relative transmittance of visible light in the wavelength range of 400 nm-700 nm as measured by the conoscopic test method described in more detail in the Examples.
[0038] The alternating transmissive and absorptive regions or the total LCF can exhibit increased relative transmittance (e.g., brightness) at a viewing angle of 0 degrees. In some embodiments, the relative transmittance (e.g., brightness) is at least 75%, 80%, 85%, or 90%. The relative transmittance (e.g., brightness) is typically less than 100%.
[0039] In other embodiments, the alternating transmissive and absorptive regions or the total LCF can exhibit low relative transmittance (e.g., brightness) at a viewing angle of 0 degrees. In some embodiments, the relative transmittance measured with a conoscope for a wavelength range of 400 nm to 700 nm at a viewing angle of 0 degrees is less than 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, or 10%.
[0040] The alternating transmission and absorption regions or the total LCF can exhibit high transmittance to light of other wavelengths at a viewing angle of 0 degrees. The transmittance of near infrared (NIR) light in the wavelength range of 700nm-1400nm and ultraviolet (UV) light in the wavelength range of 320nm-400nm refers to the transmittance measured by the spectrophotometric method described in more detail in the examples.
[0041] In some embodiments, the alternating transmissive and absorptive regions or the total LCF have a transmittance of at least 50%, 55%, 60%, 65%, 70%, 75%, or 80% at a viewing angle of 0 degrees for wavelengths in the range of 700 nm-1400 nm (NIR). In some embodiments, the alternating transmissive and absorptive regions or the total LCF have a transmittance of at least 50% or 60% at a viewing angle of 0 degrees for wavelengths in the range of 320 nm-400 nm (UV). The transmittance may be for a single wavelength within the wavelength range, or the transmittance may be the average transmittance over the entire wavelength range.
[0042] Alternatively, the alternating transmission regions and absorption regions or the total LCF may exhibit low transmittance to light of other wavelengths at a 0 degree viewing angle. The (e.g., PET) base film and material of the light-transmitting regions and the base layer may have high transmittance to visible light and NIR light, but low transmittance to UV light. In addition, including (e.g., color shifting) films can significantly reduce the transmittance to both UV light and NIR light while exhibiting high transmittance to visible light. In some embodiments, the alternating transmission regions and absorption regions or the total LCF have a transmittance of less than 50%, 45%, 40%, or 30% for wavelengths in the range of 700nm-1400nm (NIR) at a 0 degree viewing angle. In some embodiments, the alternating transmissive and absorptive regions or the total LCF has a transmittance of less than 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, or 5% for wavelengths in the range of 320nm-400nm (UV) at a viewing angle of 0 degrees. The transmittance can be for a single wavelength in the wavelength range, or the transmittance can be the average transmittance over the entire wavelength range.
[0043] In typical embodiments, the LCF has significantly lower transmittance at other viewing angles. For example, in some embodiments, the relative transmittance (e.g., visible light brightness) at a viewing angle of -30 degrees, +30 degrees, or an average of -30 degrees and +30 degrees is less than 50%, 45%, 40%, 35%, 30%, or 25%. In other embodiments, the relative transmittance (e.g., brightness) at a viewing angle of 30 degrees, +30 degrees, or an average of -30 degrees and +30 degrees is less than 25%, 20%, 15%, 10%, or 5%. In some embodiments, the relative transmittance (e.g., brightness) at a viewing angle of + / -35 degrees, + / -40 degrees, + / -45 degrees, + / -50 degrees, + / -55 degrees, + / -60 degrees, + / -65 degrees, + / -70 degrees, + / -75 degrees, or + / -80 degrees is less than 25%, 20%, 15%, 10%, or 5%, or less than 5%. In some embodiments, the average relative transmittance (e.g., brightness) for viewing angles in the range of +35 degrees to +80 degrees, -35 degrees to -80 degrees, or an average of these ranges is less than 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, or 2%.
[0044] The alternating transmissive and absorptive regions or the total LCF may exhibit significantly lower transmittance to NIR or UV wavelengths of light at other viewing angles. For example, in some embodiments, the alternating transmissive and absorptive regions or the total light control film have a transmittance of less than 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, or 5% for a wavelength range of 700nm-1400nm (NIR) at a viewing angle of 30 degrees. In some embodiments, the alternating transmissive and absorptive regions or the total light control film have a transmittance of less than 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, 5%, 4%, 3%, 2%, or 1% for a wavelength range of 320nm-400nm (UV) at a viewing angle of 30 degrees. In some embodiments, the transmittance to NIR or UV wavelengths of light at a viewing angle of 60 degrees also falls within the aforementioned ranges and is generally lower than the transmittance at 30 degrees. In some embodiments, the alternating transmissive and absorptive regions or the overall light control film has an average transmittance of less than 5%, 4%, 3%, 2%, or 1% for the wavelength range of 700 nm-1400 nm (NIR) at a 60 degree viewing angle.
[0045] Thus, the light control films described herein can exhibit various combinations of high and low transmission characteristics for various wavelengths of light (visible, UV, and NIR) at various viewing angles.
[0046] In one embodiment, the light control film exhibits high transmittance for NIR at various viewing angles (e.g., 0 degrees, 30 degrees, and 60 degrees), while exhibiting lower transmittance for visible light and UV, as previously described. The light control film may exhibit at least 60%, 65%, 70%, 75%, or 80% transmittance for wavelengths in the range of 700nm-1400nm (NIR), and at least 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50% transmittance for wavelengths in the range of 700nm-1400nm (NIR) at a viewing angle of 30 degrees and / or 60 degrees.
[0047] LCFs with significantly lower transmittance at "off-axis" viewing angles are suitable for use as privacy films. Such films allow an observer directly in front of the display (0 degree viewing angle) to see the image, but block observers from seeing such images at "off-axis" angles.
[0048] The absorptive region can be characterized relative to the maximum surface area of the absorptive region that blocks (e.g., absorbs) light at the light input surface or light output surface. The light input surface or light output surface of the light control film can be observed with an optical microscope (e.g., at 200 times magnification). For smaller absorptive regions (e.g., W A Less than 1 micron), higher resolution microscopy (e.g., scanning electron microscopy) can be used to measure the surface area. The maximum width of multiple absorption regions (i.e., Figure 1a W A ) and spacing (i.e., Figure 1a P A ) can be measured by analyzing light microscopy images with ImageJ software (such as available from the National Institute of Health at http: / / imagej.nih.gov / ij).
[0049] Figure 1c For a perspective view of comparative LCF 150, it includes a light output surface 120 and an opposing light input surface 110. The light output surface 120 is generally parallel to the light input surface 110. LCF 700 includes alternating transmissive regions 130 and absorptive regions 140 disposed between the light output surface 120 and the light input surface 110. For comparative light control film (CE2), as shown in FIG. Figure 1c As shown, the average maximum width W of the (e.g., five) absorption regions is A The average spacing P is 15 microns. A (distance between absorption areas) is 65 microns. Ratio W A / P A= 0.23 or 23%. In other words, the maximum surface area occupied by the absorptive regions is 23% of the total alternating transmissive and absorptive regions of the light output surface 720.
[0050] The absorptive regions described herein block (e.g., absorb) less light than comparable light control films. In typical embodiments, the maximum surface area occupied by the absorptive regions is less than 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, or 3% of the total alternating transmissive and absorptive regions. When the absorptive regions have a wall angle of zero or in other words a height of Figure 1a The maximum surface area occupied by the absorptive region when shown normal to the light input and light output surfaces can be calculated in the same manner as the comparative light control film just described (i.e., the ratio W A / P A ). When the absorbing region has a wall angle greater than zero, the ratio W A / P A All light that is blocked when light passes through the film in a direction normal to the light input surface and the light output surface is not considered. In this embodiment, "d" can be calculated from the wall angle and the line 160 perpendicular to the light output surface 120. This total surface area of light blocked is equal to (d + W A ) / (W T +W A ). For example, when W T When W is 30 microns, A is 0.5 microns, and the wall angle is 3 degrees, then (d+W A ) / (W T +W A ) = (tan(3°) + 0.5) / (30 + 0.5), the total surface area of blocked light is 17.1%.
[0051] Absorbent regions can be formed by coating the surface of the microstructured film. Figure 2 A microstructured film article 200 is shown that can be coated to prepare an LCF. The microstructured film shown includes a microstructured surface 210 that includes a plurality of channels 201a-201d located on a substrate layer 260. Figure 2 As shown, a continuous base layer "L" may exist between the bottom of the channel 205 and the top surface 210 of the base layer 260. Alternatively, the channel 201 may extend all the way through the microstructured film article 200. In this embodiment (not shown), the bottom surface 205 of the groove may coincide with the top surface 210 of the base layer 260. In a typical embodiment, the base layer 260 is a preformed film that includes an organic polymer material different from the transmissive region 230, as will be described subsequently.
[0052] The height and width of the protrusion (e.g., transmissive region) 230 are defined by adjacent channels (e.g., 201a and 201b). The protrusion (e.g., transmissive region) 230 may be defined by a top surface 220, a bottom surface 231, and sidewalls 232 and 233 that join the top surface to the bottom surface. The sidewalls may be parallel to each other. More typically, the sidewalls have a wall angle as described above.
[0053] In some embodiments, the protrusions (eg, transmissive regions) 230 have a pitch "P" of at least 10 microns. T The spacing is the distance between the starting point of the first protrusion (eg, the transmission area) and the starting point of the second protrusion (eg, the transmission area). Figure 2 As shown. The pitch may be at least 15 microns, 20 microns, 25 microns, 30 microns, 35 microns, 40 microns, 45 microns or 50 microns. The pitch is generally not greater than 1mm. The pitch is generally not greater than 900 microns, 800 microns, 700 microns, 600 microns or 500 microns. In some embodiments, the pitch is generally not greater than 550 microns, 500 microns, 450 microns, 400 microns, 350 microns, 300 microns, 250 microns or 200 microns. In some embodiments, the pitch is not greater than 175 microns, 150 microns, 100 microns. In a typical embodiment, the protrusions are evenly spaced and have a single pitch. Alternatively, the protrusions may be spaced so that the pitch between adjacent protrusions is not the same. In this later embodiment, at least some and usually most (at least 50%, 60%, 70%, 80%, 90% or more of the total protrusions) have the pitch just described.
[0054] The pitch P of the absorption area A In the same range as just described for the light-transmitting region.
[0055] The spacing and height of the protrusions (e.g., transmissive regions) may be important to facilitate coating the protrusions (e.g., transmissive regions) with a light absorbing coating. When the protrusions are too closely spaced, it may be difficult to evenly coat the sidewalls. When the protrusions are too far apart, the light absorbing coating may not effectively provide its intended function, such as privacy at off-axis viewing angles.
[0056] The absorbing region is formed by providing a light absorbing coating on the sidewalls of the protrusions (eg, the transmissive region) of the microstructured film. The thickness of the light absorbing coating is equal to the width W of the absorbing region. A , as previously described. The absorbing region may be formed by any method that provides a sufficiently thin, conformable light absorbing coating on the sidewalls (eg, 232, 233).
[0057] In one embodiment, the absorbent region is formed by a combination of additive and subtractive methods.
[0058] refer to Figure 3 , the light control film can be formed by providing a microstructured film 300 (such as a microstructured film 300) including a plurality of protrusions (eg, transmissive regions) defined by a top surface (eg, 320) and sidewalls (332, 333). Figure 2 The method further comprises applying a light absorbing coating 341 to the (e.g., entire) surface of the microstructured film, i.e., the top surface 320 and sidewalls 332, 333 of the protrusion (e.g., the transmission region) and the bottom surface 305 of the channel separating the protrusion (e.g., the transmission region). The method further comprises removing the coating from the top surface 320 of the protrusion (e.g., the transmission region) and the bottom surface 305 of the channel. In some embodiments, the method further comprises filling the channel with an organic polymer material 345 such as (e.g., the same as) the protrusion (e.g., the transmission region) and curing the polymerizable resin. When the channel is not filled with a cured polymerizable resin, the channel is typically filled with air.
[0059] Articles containing microstructures (e.g. Figure 2 The microstructured film article 200 shown in FIG. 2 may be prepared by any suitable method. In one embodiment, the microstructured article (e.g., Figure 2 The microstructured film article 200 shown in FIG. 2 can be prepared by a casting and curing method as described in US 8,096,667, which includes the following steps: (a) preparing a polymerizable composition; (b) depositing the polymerizable composition onto a negative microstructured molding surface (e.g., a tool) of a master mold in an amount just sufficient to fill the cavity of the master mold; (c) filling the cavity by moving a drop of the polymerizable composition between a substrate layer (e.g., a preformed film) and the master mold, at least one of which is flexible; and (d) curing the composition. The deposition temperature may be in the range of ambient temperature to about 180° F (82° C). The master mold may be a metal (such as nickel, chrome-plated or nickel-plated copper or brass) material, or may be a thermoplastic material that is stable under polymerization conditions and has a surface energy that allows the polymerized material to be cleanly removed from the master mold. When the substrate layer is a preformed film, one or more of the surfaces of the film may be optionally primed or otherwise treated to promote adhesion to the organic material of the light-transmitting area. In one embodiment, the base layer comprises a thermosetting acrylic polymer as a primer (such as available under the trade designation "Rhoplex 3208" from Dow Chemical, Midland, MI).
[0060] The polymerizable resin may include a combination of a first polymerizable component and a second polymerizable component selected from the following substances: (meth)acrylate monomers, (meth)acrylate oligomers, and mixtures thereof. As used herein, "monomer" or "oligomer" is any substance that can be converted into a polymer. The term "(meth)acrylate" refers to both acrylate compounds and methacrylate compounds. In some cases, the polymerizable composition may include (meth)acrylated polyurethane oligomers, (meth)acrylated epoxy oligomers, (meth)acrylated polyester oligomers, (meth)acrylated phenolic oligomers, (meth)acrylated acrylic oligomers, and mixtures thereof.
[0061] The polymerizable resin may be a radiation curable polymer resin, such as a UV curable resin. In some cases, polymerizable resin compositions useful in LCFs of the present invention may include polymerizable resin compositions such as those described in U.S. Pat. No. 8,012,567 (Gaides et al.), provided that these compositions meet the refractive index and absorption characteristics described herein.
[0062] The chemical composition and thickness of the substrate layer may depend on the end use of the LCF.In typical embodiments, the thickness of the substrate layer may be at least about 0.025 millimeters (mm), and may be from about 0.05 mm to about 0.25 mm.
[0063] Available substrate materials include, for example, styrene-acrylonitrile, cellulose acetate butyrate, cellulose acetate propionate, cellulose triacetate, polyethersulfone, polymethyl methacrylate, polyurethane, polyester, polycarbonate, polyvinyl chloride, polystyrene, polyethylene naphthalate, copolymers or blends based on naphthalene dicarboxylic acid, materials based on polyolefins (such as cast or oriented films of polyethylene, polypropylene and polycycloolefins), polyimides and glass. Optionally, the substrate can include a mixture or combination of these materials. In one embodiment, the substrate can be multilayered or can include dispersed components suspended or dispersed in a continuous phase.
[0064] Examples of substrate materials include polyethylene terephthalate (PET) and polycarbonate (PC). Examples of useful PET films include optical grade polyethylene terephthalate, which is available from DuPont Films, Wilmington, Del. under the trade name "Melinex 618". Examples of optical grade polycarbonate films include LEXAN 618, which is available from GE Polymershapes, Seattle Wash. TMPolycarbonate film 8010 and Panlite 1151 available from Teijin Kasei, Alpharetta Ga. In some embodiments, the substrate layer is a PET film having a thickness of 75 microns. The substrate layer may have a matte or glossy surface.
[0065] Some substrate layers can be optically active and can act as polarizing materials. Polarization of light transmitted through the film can be achieved, for example, by including a dichroic polarizer in the film material that selectively absorbs the transmitted light. Light polarization can also be achieved by including an inorganic material (such as an oriented mica wafer) or by a discontinuous phase (such as a drop-shaped light modulating liquid crystal dispersed in a continuous film) dispersed in a continuous film. As an alternative, the film can be prepared from ultra-thin layers of different materials. For example, the polarizing material in the film can be oriented along the polarization direction by using methods such as stretching the film, applying an electric field or a magnetic field, and coating techniques.
[0066] Examples of polarizing films include those described in the following patents: U.S. Pat. No. 5,825,543 (Ouderkirk et al.); U.S. Pat. No. 5,783,120 (Ouderkirk et al.); U.S. Pat. No. 5,882,774 (Jonza et al.); U.S. Pat. Nos. 5,612,820 (Shrenk et al.) and 5,486,949 (Shrenk et al.). The use of these polarizing films in conjunction with prismatic brightness enhancing films has been described, for example, in U.S. Pat. No. 6,111,696 (Allen et al.) and U.S. Pat. No. 5,828,488 (Ouderkirk et al.). Commercially available films are multilayer reflective polarizing films, such as 3M® from 3M Co. TM Double Brightness Enhancement Film "DBEF" (3M TM DualBrightness Enhancement Film).
[0067] In some embodiments, the base layer or cover film is a multilayer film that imparts a color shift effect, such as described in US 8,503,122. Suitable color shift films are described in U.S. Pat. No. 6,531,230 to Weber et al.; the document is incorporated herein by reference. Other suitable color shift films include multilayer films generated by spin coating, blade coating, dip coating, evaporation, sputtering, chemical vapor deposition (CVD), etc. Exemplary films include both organic and inorganic materials. Such films are described, for example, in U.S. Pat. Nos. 7,140,741; 7,486,019; and 7,018,713.
[0068] The multilayer optical film may be a UV reflector, a blue light reflector, a visible light reflector, or an infrared light reflector, as further described in U.S. Pat. No. 9,829,604 (Schmidt), Nov. 28, 2017, which is incorporated herein by reference.
[0069] In some embodiments, the multilayer optical film can be characterized as a UV reflective multilayer optical film (i.e., a UV reflector or UV mirror). A UV reflective multilayer optical film refers to a film that has a reflectivity at normal incidence of at least 50%, 60%, 70%, 80%, or 90% for a bandwidth in the range of 290nm to 400nm. In some embodiments, the reflectivity at normal incidence is at least 91%, 92%, 93%, 94%, 95%, 96%, 97%, or 98% for a bandwidth in the range of 290nm to 400nm. The UV reflective multilayer optical film can have low reflectivity and high transmittance for visible light. For example, the transmittance of visible light can be at least 85% or 90%.
[0070] In some embodiments, the multilayer optical film may be characterized as a UV-blue light reflecting multilayer optical film (i.e., a UV-blue light reflector or a UV-blue light mirror). A UV-blue light reflecting multilayer optical film refers to a film that has a reflectivity at normal incidence of at least 50%, 60%, 70%, 80%, or 90% for a bandwidth in the range of 350nm to 490nm. In some embodiments, the reflectivity at normal incidence is at least 91%, 92%, 93%, 94%, 95%, 96%, or 97% for a bandwidth in the range of 350nm to 490nm. The UV-blue light reflecting multilayer optical film may have low reflectivity and high transmittance for visible light with wavelengths greater than 500nm. For example, the transmittance of visible light with wavelengths greater than 500nm may be at least 85% or 90%.
[0071] In some embodiments, the multilayer optical film may be characterized as a near-infrared reflective multilayer optical film (i.e., a near-infrared reflector or a near-infrared mirror). A near-infrared reflective multilayer optical film refers to a film that has a reflectivity at normal incidence of at least 50%, 60%, 70%, 80%, or 90% for a bandwidth in the range of 870nm to 1100nm. In some embodiments, the reflectivity at normal incidence is at least 91%, 92%, 93%, or 94% for a bandwidth in the range of 870nm to 1100nm. In some embodiments, the film exhibits this same near-infrared reflectivity at a 45-degree angle. A near-infrared reflective multilayer optical film may have low reflectivity and high transmittance for visible light. For example, the transmittance of visible light may be at least 85%, 86%, 87%, or 88%.
[0072] Visible light reflecting multilayer optical film (e.g., visible light reflector or visible light mirror) refers to such a film, which has a reflectivity at normal incidence of at least 50%, 60%, 70%, 80%, or 90% for a bandwidth in the range of 400nm to 700nm. In some embodiments, the reflectivity at normal incidence is at least 91%, 92%, 93%, 94%, 95%, 96%, 97%, or 98% for a bandwidth in the range of 400nm to 700nm. The near-infrared reflectivity characteristics of such broadband reflectors are as previously described.
[0073] In other embodiments, a single multilayer optical film can reflect more than one bandwidth and can be considered a broadband reflector. For example, the multilayer optical film can be a visible light and near infrared light reflecting multilayer optical film. Therefore, such a multilayer optical film has high reflectivity for both the visible light bandwidth and the near infrared light bandwidth.
[0074] In addition, two or more multilayer optical film mirrors having different reflection bands, for example, are laminated together to broaden the reflection band. For example, a multilayer optical film visible light reflector such as described above can be combined with a UV, UV-blue light, and / or near infrared light reflector. Various other combinations can be used as will be appreciated by those of ordinary skill in the art.
[0075] Alternatively, a microstructure-containing article (e.g. Figure 2 The microstructured film article 200 shown in ) can be prepared by melt extrusion (i.e., pouring a fluid resin composition onto a negative microstructured molding surface of a master mold (e.g., a tool) and allowing the composition to harden). In this embodiment, the protrusions (e.g., light-transmitting areas) are interconnected to the base layer 260 in a continuous layer. Individual protrusions (e.g., light-transmitting areas) and the connections between them typically comprise the same thermoplastic material. The thickness of the base layer (i.e., the thickness excluding the portion produced by the replicated microstructure) is typically between 0.001 inches and 0.100 inches, and preferably between 0.003 inches and 0.010 inches.
[0076] When microstructured articles (e.g. Figure 2 When the microstructured film article 200 shown in FIG. 1 is prepared by the aforementioned casting and curing process, the thickness of the base layer can be smaller. For example, the thickness of the base layer is generally at least 0.5 microns, 1 micron, 2 microns, 3 microns, 4 microns, or 5 microns, ranging up to 50 microns. In some embodiments, the thickness of the base layer is no greater than 45 microns, 40 microns, 35 microns, 30 microns, 25 microns, 20 microns, 15 microns, or 10 microns. In one embodiment, the base layer is 8 microns.
[0077] Resin compositions suitable for melt extrusion are dimensionally stable, durable, weather-resistant, and transparent materials that can be easily formed into desired configurations. Examples of suitable materials include acrylics with a refractive index of about 1.5, such as Plexiglas brand resins manufactured by Rohm and Haas Company; polycarbonates with a refractive index of about 1.59; reactive materials such as thermosetting acrylates and epoxy acrylates; polyethylene-based ionomers and copolymers, such as those sold by EIDupont de Nemours and Co., Inc. under the trade name SURLYN; ethylene acrylic acid copolymers; polyesters; polyurethanes; fluoropolymers; silicone polymers; ethylene vinyl acetate (EVA) copolymers and cellulose acetate butyrate. Polycarbonates are particularly suitable due to their toughness and relatively high refractive index.
[0078] In another embodiment, a master negative microstructured molding surface (eg, tool) can be used as an embossing tool, such as described in US Pat. No. 4,601,861 (Pricone).
[0079] The absorbing region is typically formed by coating the surface of the microstructured film. Various coating methods can be used, including, for example, layer-by-layer coating (LbL), vapor deposition, sputtering, reactive sputtering, and atomic layer deposition (ALD).
[0080] The light absorbing material that can be used to form the light absorbing region can be any suitable material used to absorb or block light in at least a portion of the visible spectrum. In a typical embodiment, the light absorbing material also absorbs or blocks at least a portion of the UV and / or IR spectrum. Preferably, the light absorbing material can be coated or otherwise provided on the sidewalls of the light-transmitting region to form the light absorbing region in the LCF. Exemplary light absorbing materials include black or other light absorbing colorants (such as carbon black, or another pigment or dye, or a combination thereof). Other light absorbing materials may include particles or other scattering elements that can be used to block light from being transmitted through the light absorbing region.
[0081] When the light absorbing material (eg, coating) includes particles, the median particle size D50 of the particles is equal to or less than the thickness of the light absorbing material (eg, coating) or in other words substantially less than the width W of the absorbing region. A .
[0082] The median particle size is generally less than 1 micron. In some embodiments, the median particle size is not more than 900nm, 800nm, 700nm, 600nm or 500nm. In some embodiments, the median particle size is not more than 450nm, 400nm, 350nm, 300nm, 250nm, 200nm or 100nm. In some embodiments, the median particle size is not more than 90nm, 85nm, 80nm, 75nm, 70nm, 65nm, 60nm, 55nm or 50nm. In some embodiments, the median particle size is not more than 30nm, 25nm, 20nm or 15nm. The median particle size is generally at least 1 nanometer, 2 nanometers, 3 nanometers, 4 nanometers or 5 nanometers. For example, the particle size of the nanoparticles in the absorption region can be measured using a transmission electron microscope or a scanning electron microscope.
[0083] "Primary particle size" refers to the median diameter of a single (non-aggregated, non-agglomerated) particle. "Agglomeration" refers to a weak association between primary particles, which can be held together by charge or polarity and can be broken down into smaller entities. "Agglomerates" as used herein relative to particles refer to strongly bonded or fused particles, wherein the resulting surface area can be significantly less than the sum of the calculated surface areas of the individual components. The forces holding the aggregates together are very strong forces, such as covalent bonds, or forces generated by sintering or complex physical entanglements. Although agglomerated nanoparticles can be broken down into smaller entities such as discrete primary particles, such as by applying a surface treatment; applying a surface treatment to the aggregates only results in surface-treated aggregates. In some embodiments, most nanoparticles (i.e., at least 50%) exist as discrete, unagglomerated nanoparticles. For example, at least 70%, 80%, or 90% of the nanoparticles (e.g., of a coating solution) exist as discrete, unagglomerated nanoparticles.
[0084] The concentration of light absorbing nanoparticles is typically at least 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50% by weight of the total light absorbing area. In some embodiments, the concentration of light absorbing nanoparticles is at least 55%, 60%, 65%, 70%, or 75% by weight of the total light absorbing area. The concentration of light absorbing nanoparticles can be determined by methods known in the art, such as thermogravimetric analysis.
[0085] In one embodiment, the method includes applying layer-by-layer light absorbing coatings to the surface of the microstructured film, ie, the top surfaces and sidewalls of the protrusions and the bottom surfaces of the channels.
[0086] In some embodiments, the plurality of layers disposed on the surface of the microstructured film include at least two layers deposited by what is commonly referred to as a "layer-by-layer self-assembly process". This process is typically used to electrostatically assemble films or coatings of oppositely charged polymer electrolytes, but other functions such as hydrogen bond donors / acceptors, metal ions / ligands, and covalent bond moieties can be the driving force for film assembly. "Polymer electrolyte" means a polymer or compound with multiple ionic groups capable of electrostatic interactions. "Strong polymer electrolytes" have a persistent charge over a wide pH range (e.g., polymers contain quaternary ammonium groups or sulfonic acid groups). "Weak polymer electrolytes" have a pH-dependent level of charge (e.g., polymers contain primary, secondary or tertiary amines, or carboxylic acids). Typically, the deposition process involves exposing a substrate having a surface charge to a series of liquid solutions or baths. This can be achieved by immersing the substrate in a liquid bath (also referred to as dip coating), spraying, spin coating, roller coating, inkjet printing, etc. Exposure to a first polyion (e.g., polymer electrolyte bath) liquid solution having an opposite charge to the substrate results in rapid adsorption of charged species near the substrate surface, establishment of a concentration gradient, and absorption of more polymer electrolytes from the bulk solution to the surface. Further adsorption occurs until enough layers have developed to mask the underlying charge and reverse the net charge on the substrate surface. In order to achieve mass transfer and adsorption, the exposure time is typically on the order of minutes. The substrate is then removed from the first polyion (e.g., bath) liquid solution and then exposed to a series of water rinse baths to remove any physically entangled or loosely bound polyelectrolytes. After these rinses (e.g., bath) liquid solutions, the substrate is then exposed to a second polyion (e.g., polymer electrolyte or inorganic oxide nanoparticle bath) liquid solution having an opposite charge to the first polyion (e.g., bath) liquid solution. Since the surface charge of the substrate is opposite to that of the second (e.g., bath) liquid solution, adsorption occurs again. Continued exposure to the second polyion (e.g., bath) liquid solution causes a reversal of the surface charge of the substrate. Subsequent rinses may be performed to complete the cycle. This series of steps is referred to as building a layer pair, also referred to herein as a deposited "bilayer," and can be repeated as needed to further add additional layer pairs to the substrate.
[0087] Some examples of suitable methods include those described in US 8,234,998 to Krogman et al.; US 2011 / 0064936 to Hammond-Cunningham et al.; and US 8,313,798 to Nogueira et al. Layer-by-layer dip coating can be performed using a StratoSequence VI (nanoStrata Inc., Tallahassee, FL) dip coating robot.
[0088] In one embodiment, the plurality of bilayers deposited by layer-by-layer self-assembly is a polymer electrolyte stack comprising an organic polymer polyion (e.g., cation) containing a light absorbing material (e.g., pigment) and a counterion (e.g., anion). At least a portion of the cationic layer, at least a portion of the anionic layer, or at least a portion of a combination thereof comprises a light absorbing material (e.g., pigment) ionically bonded to the polymer electrolyte.
[0089] The thickness of the bilayer and the number of bilayers are selected to achieve the desired light absorption. In some embodiments, the thickness of the bilayer, the number of bilayers are selected to achieve the desired (e.g., absorption) optical properties using the self-assembled layer with the minimum total thickness and / or the minimum number of layer-by-layer deposition steps. The thickness of each bilayer is typically in the range of about 5 nm to 350 nm. The number of bilayers is typically at least 5, 6, 7, 8, 9, or 10. In some embodiments, the number of bilayers in each stack is no more than 150 or 100. The thickness of the stack is equal to the width W of the absorption region. A , as mentioned before.
[0090] The light absorbing compound is dispersed in at least a portion of the polymer electrolyte layer. Various polymer electrolytes can be utilized, including inorganic compounds such as silica or silicates, and various phosphonocarboxylic acids and their salts (some of which are described in WO2015 / 095317; which is incorporated herein by reference).
[0091] Polyelectrolyte organic polymers may be preferred because such materials can be removed more easily by reactive ion etching than inorganic materials.
[0092] Suitable polycationic organic polymers include, but are not limited to, linear and branched poly(ethyleneimine) (PEI), poly(allylamine hydrochloride), polyvinylamine, chitosan, polyaniline, polyamidoamine, poly(vinylbenzyltrimethylamine), polydiallyldimethylammonium chloride (PDAC), poly(dimethylaminoethyl methacrylate), poly(methacrylamido)propyl-trimethylammonium chloride, and combinations thereof, including copolymers thereof.
[0093] Suitable polyanionic organic polymers include, but are not limited to, poly(vinyl sulfate), poly(vinyl sulfonate), poly(acrylic acid) (PAA), poly(methacrylic acid), poly(styrene sulfonate), dextran sulfate, heparin, hyaluronic acid, carrageenan, carboxymethylcellulose, alginate, sulfonated tetrafluoroethylene-based fluoropolymers such as Poly(vinyl phosphoric acid), poly(vinyl phosphonic acid), and combinations thereof, including copolymers thereof.
[0094] The molecular weight of the polymer electrolyte polymer can vary in the range of about 1,000 g / mol to about 1,000,000 g / mol. In some embodiments, the molecular weight (Mw) of the negatively charged anion layer (e.g., poly(acrylic acid)) is in the range of 50,000 g / mol to 150,000 g / mol. In some embodiments, the molecular weight (Mw) of the positively charged cationic layer (e.g., polydiallyldimethylammonium chloride) is in the range of 50,000 g / mol to 300,000 g / mol. In some embodiments, the molecular weight (Mw) of the positively charged cationic layer (e.g., poly(ethyleneimine)) is in the range of 10,000 g / mol to 50,000 g / mol.
[0095] At least one of the polyions (eg, polyanions or polycations) comprises a light absorbing material.
[0096] In order to be stable in water as a colloidal dispersion and to impart polyionic groups, the light absorbing (e.g., pigment) particles generally also include an ionic surface treatment. In some embodiments, the surface treatment compound is anionic, such as in the case of sulfonates or carboxylates. The light absorbing (e.g., pigment) particles also serve as ionic binding groups for alternating polymer electrolyte layers.
[0097] Suitable pigments are commercially available as colloidally stable aqueous dispersions from manufacturers such as Cabot, Clariant, DuPont, Dainippon and DeGussa. Particularly suitable pigments include those sold under the trade names Those available from Cabot Corporation, such as 250C (cyan), 260M (magenta), 270Y (yellow), or 352K (black). The light absorbing (e.g., pigment) particles are typically surface treated to impart ionizable functionality. Examples of suitable ionizable functionality for light absorbing (e.g., pigment) particles include sulfonate functionality, carboxylate functionality, and phosphate or bisphosphonate functionality. In some embodiments, surface treated light absorbing (e.g., pigment) particles having ionizable functionality are commercially available. For example, light absorbing (e.g., pigment) particles commercially available from Cabot Corporation under the trade names 250C (cyan), 260M (magenta), 270Y (yellow), and 200 (black) are commercially available from Cabot Corporation. The pigment includes sulfonate functionality. For example, it is commercially available from Cabot Corporation under the trade names 352K (black) and 300 (black). The pigment includes carboxylate functionality.
[0098] When the light absorbing (eg, pigment) particles are not pre-treated, the light absorbing (eg, pigment) particles can be surface treated to impart ionizable functionality as is known in the art.
[0099] Multiple light absorbing materials (eg, pigments) may be used to achieve a specific chromaticity or hue or color in the final product. When multiple light absorbing materials (eg, pigments) are used, the materials are selected to ensure both their compatibility and performance with each other and with the optical product components.
[0100] In some embodiments, such as when the absorption region contains carbon black, the light control film generally provides low transmittance (e.g., less than 10%) for wavelengths in the range of 300nm to 2400nm at a 30-degree viewing angle. When the absorption region is colored, the light control film may exhibit a higher average transmittance. For example, for wavelengths in the range of 300nm to 2400nm, the transmittance at a 30-degree viewing angle may be 10% to 30%. However, a specific wavelength range may exhibit a lower transmittance within the wavelength range of the color of the absorption region. In some embodiments, the transmittance for wavelengths in the range of 300nm to 550nm at a 30-degree viewing angle is less than 15%. In some embodiments, the transmittance for wavelengths in the range of 600nm to 750nm at a 30-degree viewing angle is less than 5%, 4%, 3%, 2%, or 1%.
[0101] In a favorable embodiment, a polymer electrolyte is prepared and applied to the microstructured surface as an aqueous solution. The term "aqueous" means that the liquid of the coating comprises at least 85% by weight of water. It may comprise a higher amount of water, such as, for example, at least 90% by weight, 95% by weight, or even at least 99% by weight of water or more. The aqueous liquid medium may comprise a mixture of water and one or more water-soluble organic cosolvents, and their amount makes the aqueous liquid medium form a single phase. The example of a water-soluble organic cosolvent includes methanol, ethanol, isopropanol, 2-methoxyethanol, 3-methoxypropanol, 1-methoxy-2-propanol, tetrahydrofuran, and ketone or ester solvents. The amount of the organic cosolvent is generally no more than 15% by weight of the total liquid of the coating composition. The aqueous polymer electrolyte composition for layer-by-layer self-assembly generally comprises at least 0.01% by weight, 0.05% by weight, or 0.1% by weight, and is generally not more than 5% by weight, 4% by weight, 3% by weight, 2% by weight, or 1% by weight of the polymer electrolyte.
[0102] In some embodiments, the aqueous solution also includes a "masking agent", an additive that promotes uniform and reproducible deposition by increasing ionic strength and reducing interparticle electrostatic repulsion. Suitable masking agents include any low molecular weight salts, such as halide salts, sulfates, nitrates, phosphates, fluorophosphates, etc. Examples of halide salts include chloride salts such as LiCl, NaCl, KCl, CaCl2, MgCl2, NH4Cl, etc., bromide salts such as LiBr, NaBr, KBr, CaBr2, MgBr2, etc., iodide salts such as LiI, NaI, KI, CaI2, MgI2, etc., and fluoride salts such as NaF, KF, etc. Examples of sulfates include Li2SO4, Na2SO4, K2SO4, (NH4)2SO4, MgSO4, CoSO4, CuSO4, ZnSO4, SrSO4, Al2(SO4)3, and Fe2(SO4)3. Organic salts such as (CH3)3CCl, (C2H5)3CCl, etc. are also suitable masking agents.
[0103] Suitable masking agent concentrations may vary with the ionic strength of the salt. In some embodiments, the aqueous solution comprises a masking agent (eg, NaCl) at a concentration ranging from 0.01 M to 0.1 M. The absorption region may comprise trace amounts of the masking agent.
[0104] After the light absorbing coating is applied to the (e.g., entire) surface of the microstructured film and dried, the light absorbing coating is then removed from the top portion of the transmissive (e.g., protrusion) regions and also removed from the land regions between the transmissive (e.g., protrusion) regions. It should be understood that the LCF can have improved axial transmittance (e.g., brightness) even if some of the light absorbing coating remains.
[0105] Any suitable method may be used to selectively remove the light absorbing material from the top surfaces of the protrusions (eg, the light absorbing regions) and the bottom surfaces of the trenches.
[0106] In one embodiment, the light absorbing material is removed by reactive ion etching. Reactive ion etching (RIE) is a directional etching process that utilizes ion bombardment to remove material. RIE systems are used to remove organic or inorganic materials by etching surfaces orthogonal to the direction of ion bombardment. The most significant difference between reactive ion etching and isotropic plasma etching is the etching direction. Reactive ion etching is characterized in that the ratio of the vertical etching rate to the lateral etching rate is greater than 1. The system for reactive ion etching is built around a durable vacuum chamber. Before starting the etching process, the chamber is evacuated to a base pressure of less than 1 Torr, 100 mTorr, 20 mTorr, 10 mTorr or 1 mTorr. The electrode holds the material to be processed and is electrically isolated from the vacuum chamber. The electrode may be a rotatable electrode in the shape of a cylinder. The counter electrode is also disposed in the chamber and may be formed by the vacuum reactor wall. A gas containing an etchant enters the chamber through a control valve. The process pressure is maintained by continuously evacuating the chamber gas by a vacuum pump. The type of gas used depends on the etching process. Carbon tetrafluoride (CF4), sulfur hexafluoride (SF6), octafluoropropane (C3F8), trifluoromethane (CHF3), boron trichloride (BCl3), hydrogen bromide (HBr), chlorine, argon and oxygen are commonly used for etching. RF power is applied to the electrode to generate a plasma. The sample can be transported over the electrode by the plasma for a controlled period of time to achieve a specified etching depth. Reactive ion etching is known in the art and is further described in US 8,460,568; the document is incorporated herein by reference.
[0107] In some embodiments, the step of reactive ion etching causes the absorbing region to be narrower (less than average width) near the bottom surface 311 of the trench. Removing the light absorbing material can cause the depth of the trench to increase (eg, slightly). Some of the light absorbing material can remain after etching.
[0108] After removing the light absorbing coating from the bottom surface of the channel, the channel can be filled with an organic polymer material. In some embodiments, the organic polymer material is a polymerizable resin composition, and the method further comprises (e.g., radiation) curing the polymerizable resin. Typically, the same polymerizable resin used to make the microstructured film is used to fill the channel. Alternatively, different organic polymer materials (e.g., polymerizable resin compositions) are used. When different organic polymer materials (e.g., polymerizable resin compositions) are used, the composition is typically selected to match the refractive index of the light-transmitting region. The so-called "refractive index matching" means that the refractive index difference between the filling material and the transmission region is typically less than 0.1 or 0.005. Alternatively, the channel can be filled with different organic polymer materials (e.g., polymerizable resin compositions) having a refractive index difference greater than 0.1. In another embodiment, the channel is not filled with an organic polymer material (e.g., a polymeric resin). In this embodiment, the channel typically includes air with a refractive index of 1.0.
[0109] When the channels are filled with a cured polymerizable resin, the light management film can optionally include a cover film 470 bonded to the microstructured film with adhesive 410. When the channels are filled with air, an adhesive film and a cover film are typically included.
[0110] In another embodiment, layer 410 may be a topcoat rather than an adhesive. In this embodiment, cover film 470 may not be present.
[0111] Figure 4 LCF 400 is shown further comprising an optional cover film 470 that may be the same as or different from base layer 260. Optional cover film 470 may be bonded to the microstructured surface with adhesive 410. Adhesive 410 may be any optically clear adhesive such as a UV curable acrylate adhesive, a transfer adhesive, and the like.
[0112] Alternatively, the cover film may be in contact with a polymerizable resin (eg, backfill resin) for filling the trench. The backfill resin is cured while in contact with the cover film, thereby bonding the cover film.
[0113] One or more of the surfaces of the cover film may optionally be primed or otherwise treated to promote adhesion with the adhesive or backfill resin.
[0114] In typical embodiments, the cover film may have a thickness of at least about 0.025 mm (25 microns), and may be about 0.05 mm (50 microns) to about 0.25 mm (250 microns). In some embodiments, the cover film is a multilayer wavelength (eg, color) shifting film as previously described.
[0115] In some embodiments, the LCF includes a light absorbing layer or a light reflecting layer between the alternating transmissive and absorptive regions and the light input surface or the light output surface, rather than the wavelength shifting film described above.
[0116] In some embodiments, the light absorbing layer includes a pigment and / or a dye. For example, the substrate layer and / or the cover film may include a pigment and / or a dye. In yet another embodiment, an adhesive layer may be present to bond the cover film to the LCF. In this embodiment, the adhesive may include a pigment and / or a dye. In yet another embodiment, the absorbing layer may be a coating applied (e.g., coated or printed) to the top or bottom surface of the alternating transmission regions and absorption regions, the main surface of the substrate layer, or the main surface of the cover film. In a favorable embodiment, the adhesive or coating is located between the cover film and the alternating transmission regions and absorption regions. The coating is typically not an anti-glare coating or an anti-reflective coating. On the contrary, the coating typically includes a pigment or a dye so that the coating is wavelength selective.
[0117] In another embodiment, the alternating transmissive regions include an absorptive material, such as a pigment or dye.
[0118] A variety of light absorbing or reflective materials can be used. For example, clearly transparent infrared absorbing transparent conductive oxides (TCOs) can be used as thin films or as nanoparticle powders and dispersions. Exemplary TCOs include indium tin oxide (ITO), antimony tin oxide (ATO), gallium tin oxide (GTO), antimony zinc oxide (AZO), aluminum / indium doped zinc oxide, doped tungsten oxides such as cesium tungsten oxide and tungsten blue oxide. Other clearly transparent infrared absorbers include metal borides such as lanthanum hexaboride and conductive polymer nanoparticles such as PEDOT-PSS. Metal chalcogenides such as metal sulfides and selenides also absorb infrared light, including, for example, copper sulfide and copper selenide nanoparticles, tungsten disulfide and molybdenum disulfide. Another class of clearly transparent tunable infrared absorbers are metal plasma nanoparticles, such as those made of gold, silver, copper, etc. Near-infrared dyes and pigments can be applied to the disclosed LCFs. These dyes have low visible absorption but strong narrow-band infrared absorption. Many of these dyes and pigments are organic / organic metal or metal organic in nature. Some kinds in the dyestuff / pigment of main kind comprise phthalocyanine, cyanine, transition metal dithioline, squarylium, keto acid, quinone, anthraquinone, imine, pyridine, thiopyran (thiapyrilium), azulene (azulenium), azo, perylene and indoaniline.Many in these dyestuff and pigment also can show visible light and / or infrared light absorption.In addition, many different types of visible dyes and coloring agents can be used, such as acid dyes, azo coloring agents, coupling components, diazo components.Basic dye comprises developer, direct dye, disperse dye, fluorescent whitening agent, food dye, color developing dye, leather dye, mordant dye, natural dye and pigment, oxidation alkali, pigment, reactive dye, reducing agent, solvent dye, sulfur dye, sulphur dye, vat dye. Some organic pigments in organic pigments can be one or more of monoazo, azo condensation insoluble metal salts of acid dyes and disazo, naphthol, aryl compound, diarylate, pyrazolone, acetylaryl compound, naphthylanilide, phthalocyanine, anthraquinone, perylene, anthraquinone, trianthraquinone, metal complex, quinacridone, polypyrrole, etc. Metal oxide pigments can be used, such as metal chromate, molybdate, titanate, tungstate, aluminate, ferrite. Many contain transition metals, such as iron, manganese, nickel, titanium, vanadium, antimony, cobalt, lead, cadmium, chromium, etc. Bismuth vanadate is non-cadmium yellow. These pigments can be ground to produce nanoparticles, which can be used in the case of needing transparency and low scattering.
[0119] Combinations of colorants can produce a broad spectrum of colors.In some embodiments, the light reflecting or absorbing layer includes little or no carbon black (eg, less than 0.5%).
[0120] In some examples, particulate light absorbing materials and / or particulate light reflecting materials having an average particle size of less than 10 microns, or 1 micron, or less are used. In some embodiments, the particulate light absorbing materials and / or particulate light reflecting materials have an average particle size of less than 1 micron. In some embodiments, the particulate light absorbing materials and / or particulate light reflecting materials may be dispersed in a suitable binder.
[0121] In some embodiments, the light absorbing materials are anthraquinone dyes (e.g., Pigment Yellow 147, Solvent Yellow 163, Pigment Blue 60, Pigment Red 177), perylene dyes (e.g., Pigment Black 31, Pigment Black 32, Pigment Red 149), and quinacridone dyes (e.g., Pigment Red 122); such as described in US 9,630,384; which is incorporated herein by reference.
[0122] In some embodiments, the light absorbing material is a UV absorber. The UV absorber works by preferentially absorbing UV radiation and dissipating it as heat. Suitable UVAs may include: benzophenones (hydroxybenzophenones, such as Cyasorb 531 (Cytec); benzotriazoles (hydroxyphenylbenzotriazoles, such as Cyasorb 5411, Tinuvin 329 (Ciba Geigy); triazines (hydroxyphenyltriazines, such as Cyasorb 1164), oxanilides (e.g., Sanuvor VSU (Clariant); cyanoacrylates (e.g., Uvinol 3039 (BASF)) or benzoxazinones. Suitable benzophenones include CYASORB UV-9 (2-hydroxy-4-methoxybenzophenone), CHIMASSORB 81 (or CYASORB UV 531) (2-hydroxy-4-octyloxybenzophenone). Suitable benzotriazole UVAs include compounds available from Ciba, Tarrytown, NY under the trade designations TINUVIN P, 213, 234, 326, 327, 328, 405, and 571, and CYASORB UV 5411 and CYASORB UV 237. Other suitable UVAs include CYASORB UV 1164 (2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2yl]-5(octyloxy)phenol) (an exemplary triazine) and CYASORB 3638 (an exemplary benzotriazine).
[0123] When the light absorbing material is a UV absorber, it is typically present in the cover film rather than in the UV curable polymerizable resin.
[0124] The concentration of light absorbing materials (e.g., pigments, dyes, UV absorbers) can vary. In some embodiments, the concentration of light absorbing materials (e.g., dyes) is no greater than 10%, 9%, 8%, 7%, 6%, or 5% by weight of the substrate (e.g., preformed film) layer, adhesive, coating, cover film, or light transmissive (e.g., backfill) material.
[0125] The thickness of these various light absorbing layers can vary. In some embodiments, the thickness is typically at least about 0.025 mm (25 microns), and can be about 0.05 mm (50 microns) to about 0.25 mm (250 microns). When the light absorbing layer is an adhesive or coating, the thickness can be less than 25 microns. For example, the thickness can be at least 5 microns, 10 microns, 15 microns, or 20 microns, ranging up to 50 microns. The adhesive or coating can be a continuous layer or a discontinuous layer.
[0126] In some embodiments, the light reflecting or absorbing layer is a (e.g., cover layer or substrate layer) preformed film. For example, in one embodiment, the LCF includes a cover film or substrate layer film, and the cover film or substrate layer film is an optical diffuser. The optical diffuser can help scatter light incident on the LCF (especially at high angles of incidence) into the light-transmitting region and toward the detector.
[0127] The LCF may also include other coatings, which are typically disposed on the exposed surface. Various hard coatings, anti-glare coatings, anti-reflective coatings, anti-static coatings, and anti-fouling coatings are known in the art. See, for example, U.S. Pat. No. 7,267,850; U.S. Pat. No. 7,173,778, PCT Publications WO2006 / 102383, WO2006 / 025992, WO2006 / 025956, and U.S. Pat. No. 7,575,847.
[0128] Figure 5 A perspective schematic diagram of a backlight display 500 according to one embodiment is shown. The backlight display 500 includes an LCF 530 including a transmissive region 540 and an absorptive region 550 as previously described. As previously described, such an LCF has a polar cutoff viewing angle θP for light leaving an output surface 590 of the LCF 530. The backlight display 500 includes a light source 510 configured to send light through the LCF 530, through an image plane 520 (such as an LCD panel), and to an observer 595. The viewing angle at which the brightness is maximum may depend on the polar cutoff viewing angle as previously described.
[0129] The backlit display 500 may also include an optional brightness enhancement film 560 and a reflective polarizing film 570 to further improve the brightness and uniformity of the display. The brightness enhancement film may be a prismatic film, such as 3M TM Brightness Enhancement Film (3M TMBrightness Enhancement Film (BEF) or Thin Brightness Enhancement Film (TBEF). The reflective polarizing film 570 can be a multilayer optical film, such as 3M Co., Ltd., available from 3M Company, St. Paul, MN. TM Dual Brightness Enhancement Film "DBEF". Brightness enhancement film 560 and reflective polarizing film 570 (if included) may be as shown. Figure 5 Positioning shown.
[0130] In other embodiments, as previously described, a light management film including transmissive and absorptive regions can be bonded to an emissive (eg, organic light emitting diode or OLED) display.
[0131] In some embodiments, the LCF described herein (i.e., the first LCF) can be combined with a second LCF. In some embodiments, the second LCF can be an LCF such as described in the following patents (e.g., a privacy film): US 6,398,370; US 8,013,567; US 8,213,082; and US 9,335,449. In other embodiments, the second LCF is an LCF as described herein (e.g., wherein the light absorbing region has an aspect ratio of at least 30). The first LCF and the second LCF can be stacked in various orientations.
[0132] In one embodiment, the first and second light control films are positioned so that the absorption region of the first LCF is parallel and generally coincident with the absorption region of the second LCF. In another embodiment, the first and second light control films are positioned so that the absorption region of the first LCF is orthogonal to the absorption region of the second LCF. The first and second light control films can also be positioned so that the absorption regions are in a range from parallel to orthogonal to each other at a viewing angle of 0 degrees.
[0133] In some embodiments, the combination of the first LCF and the second LCF has a relative transmittance (e.g., brightness) of at least 60%, 65%, 70%, 75%, 80%, 85%, or 90% at a viewing angle of 0 degrees. In some embodiments, the relative transmittance (e.g., brightness) at a viewing angle of +30 degrees, -30 degrees, or an average of +30 degrees and -30 degrees is less than 25%, 20%, 15%, 10%, or 5%. In some embodiments, the average relative transmittance (e.g., brightness) for viewing angles in the range of +35 degrees to +80 degrees, -35 degrees to -85 degrees, or an average of these ranges is less than 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, or 1%.
[0134] When the channels are filled with air, the relative transmittance (eg, brightness) at higher viewing angles may be lower, and thus the film may exhibit improved privacy.
[0135] In some embodiments, the light control films described herein are particularly useful as components of display devices as so-called hybrid privacy filters. The hybrid privacy filter can be used in conjunction with a display surface, where light enters the hybrid privacy filter on the input side of the light control film and exits the hybrid privacy filter or film stack at the color shifting film. A large number of electronic devices with displays can be used in conjunction with the present invention, including laptop monitors, external computer monitors, mobile phone displays, televisions, smart phones, automotive center information displays, automotive driver information displays, automotive side mirror displays (also known as electronic mirrors), consoles, or any other similar LCD, OLED, micro-LED or mini-LED based displays. An additional benefit of applying a hybrid privacy filter to a display is contrast enhancement.
[0136] Other types of backlit display imaging devices are also contemplated, including non-electronic displays such as sunglasses, document covers, console switches in automotive and aviation applications, aircraft cockpit controls, helicopter cockpit controls, windows, and any number of other devices.
[0137] In other embodiments, the light control films described herein can be used as coatings for glass and solar panels. For example, the light control films can be laminated onto or into door and window facilities. Door and window facilities can be selected from glass panels, windows, doors, walls, and skylight devices. Door and window facilities can be located on the exterior or interior of a building. These facilities can also be car windows, train windows, aircraft passenger windows, ATMs, etc. The advantages of assembling these film stacks into door and window facilities include reduced IR transmission (which can lead to increased energy savings), blocking ambient light, privacy, and decorative effects.
[0138] In some embodiments, the light control film (LCF) described herein can be part of an optical communication system. The "optical communication system" mentioned herein is a system for optical communication of the distance from a light source to a target through a disclosed LCF, wherein the target may include a detector or a human eye, and the light source may include ambient light. Exemplary light sources include light emitting diodes (LEDs) emitting UV, visible light or NIR, laser light sources including VCSELs (vertical cavity surface emitting lasers), halogen light sources, incandescent light sources, metal halide light sources, tungsten light sources, mercury vapor light sources, short arc xenon light sources, or the sun (solar energy). In some cases, the LCF disclosed herein can be part of an optical communication system with a detector system. In some cases, when receiving light from the LCF passing through the optical communication system, the detector system can provide various types of outputs, such as electronic signals. The detector system includes a detector sensitive to wavelengths within the detection wavelength range and an LCF disposed on the detector.
[0139] In some embodiments, the detector is or includes a photovoltaic device. In some cases, the detector is configured to detect solar radiation, for example, to charge a battery pack. In such cases, the detector is or may include a solar cell group, a solar cell, an organic silicon photodiode, or a solar detector. In some cases, the detector may be a detector for detecting and / or recording images in a (for example, visible light or near infrared) camera. In some cases, the detector may be in a camera or camera system. Other detectors include CMOS (complementary metal oxide semiconductor) and CCD (charge coupled device) detectors. Typical applications of light detectors (also referred to herein as sensors) include gesture recognition, iris recognition, facial recognition, remote control and autonomous vehicles, ambient light sensors, proximity sensors, heart rate, blood oxygen, glucose or other biosensing, 3D depth cameras with time of flight or structured light, and security cameras.
[0140] In some cases, the light control films (LCFs) disclosed herein may be part of an optical communication system including, for example, Figure 7 The optical construction of the window combination shown. In this example, LCF 600 is part of an optical construction 601 with a natural light source such as sunlight 690. Specifically, Figure 7An exemplary application of the disclosed LCF is shown, which is applied to a window of an enclosure such as a building, a house, or a vehicle. The LCF 600 can be disposed on a window substrate 675 of a building, a house, a car, or any enclosure 670. The LCF 600 includes an optical film 650 including a plurality of spaced-apart first absorptive regions 630 and an optical second (e.g., cover film) region 640 adjacent to at least a portion of at least one of the first regions 630. The first region 630 includes a first absorptive material 632, and the second region 640 may include a second material 642.
[0141] In advantageous embodiments, the LCF window film exhibits high transmittance for visible light and low transmittance for UV and NIR light.
[0142] The transmittance of the first absorption region 630 to ultraviolet light and infrared light varies depending on the incident angle of the light. Specifically, when sunlight 690 is incident perpendicular to the LCF 600, both infrared light and visible light can be transmitted through the optical film 650. However, as the incident angle of the light from the sun 690 increases, the amount of infrared light transmitted through the LCF 600 decreases until the incident angle reaches a viewing angle θP, at which time substantially all infrared light is blocked by the first material 632. That is, during the morning hours, when the infrared portion of the sunlight 690 is relatively small and the sunlight 690 is incident on the window at a normal angle of incidence, most of the infrared light can be transmitted by the LCF 600. On the other hand, near noon, when the infrared portion of the sunlight 690 is relatively large and the incident angle of the sunlight 690 increases to approach or exceed the viewing angle 2θv of the LCF 600, very little incident infrared light is transmitted by the LCF 600 and is eventually blocked, so that an observer or resident 677 in the building or house 670 may not be exposed to thermal infrared light. Therefore, the LCF 600 can reduce exposure to ultraviolet light and infrared light.
[0143] Figure 8 The relationship between the detector sensitivity and the wavelength is schematically shown, thereby showing that the detector is sensitive to wavelengths within the detection wavelength range. Figure 8As shown, each first region of the LCF disclosed in the present invention may have a substantially high transmittance within a predetermined first wavelength range "A", a substantially low transmittance within a predetermined second wavelength range "B", and a substantially high transmittance within a predetermined third wavelength range "C", wherein the second wavelength ranges B are respectively disposed between the first wavelength range A and the third wavelength range C. In some cases, the second wavelength range B is about 20 nm wide from the first wavelength 712 to the second wavelength 714 and is centered on the laser visible emission wavelength, the first wavelength range A is about 400 nm to about the first wavelength 712, and the third wavelength range C is about the second wavelength 714 to about 1400 nm. The laser visible emission wavelength may be at least one of 442 nm, 458 nm, 488 nm, 514 nm, 632.8 nm, 980 nm, 1047 nm, 1064 nm, and 1152 nm. In other examples, the laser visible emission wavelength is in the range of about 416 nm to about 1360 nm. In other examples, the LCF may also include a plurality of spaced-apart second regions alternating with a plurality of first regions, and each second region may have a substantially high transmittance within each of a predetermined first wavelength range, a second wavelength range, and a third wavelength range. In other examples, each second region may have a substantially low transmittance within either / both of the predetermined first wavelength range or / and the third wavelength range. In some cases, the LCF has a viewing angle of less than about 60 degrees, or 50 degrees, or 40 degrees, or 30 degrees, or 20 degrees within a predetermined second wavelength range.
[0144] In another exemplary application, the LCF disclosed herein may be a light source with a separate light source such as Figure 8 The laser light source shown is part of an optical communication system.
[0145] Specifically, Fig. 9 An exemplary application is shown in which the LCF is applied to an aircraft or aircraft laser strike defense system to block incoming light or incident light within a predetermined wavelength range. The LCF 800 can be attached to, for example, an aircraft, aircraft, or aircraft 870, and is desirably attached to a surface (such as a window) of the aircraft, aircraft, or aircraft 870. The LCF 800 includes an optical film 850 that includes a plurality of spaced-apart first absorptive regions 830 and an optical second (e.g., cover film) region 840 adjacent to at least a portion of at least one of the first regions 830. The first region 830 includes a first absorptive material 832, and the second region 840 includes a second material 842.
[0146] When laser light 891 is incident on LCF 800, second (e.g., cover film) material 842 absorbs and / or reflects at least a portion of the ultraviolet and infrared wavelength ranges, regardless of the incident angle of light 891. In addition, second (e.g., cover film) region 840 transmits in the visible light wavelength range including the wavelength of laser light 891, but the transmittance of visible light through first region 830 varies as a function of the incident angle of the light. When light is incident perpendicular to the surface of LCF 800, visible light can be transmitted through optical film 850. However, at a viewing angle θP (reference angle θP), the visible light can be transmitted through optical film 850. Figure 1b ), visible light is blocked by the first absorbing material 832 in the first region 830. Therefore, when the LCF 800 is used on an aircraft or aircraft 870, visible light from the laser 891 within the viewing angle θP may be transmitted by the LCF 800, but ultraviolet light and infrared light from the laser 891 may not be transmitted by the LCF 800 or only a limited amount of ultraviolet light and infrared light may be transmitted, desirably less than about 10% of ultraviolet light and infrared light, respectively, may be transmitted by the LCF 800. Visible light may be transmitted by the LCF 800 as a function of the incident angle of the light, including the wavelength. The laser impactor 878 may, for example, attack the aircraft or aircraft 870 using a green laser 890 to block the view of the pilot 877. Typically, the wavelength of green is about 495nm to 570nm. Thus, when the LCF 800 includes a first absorbing material 832 that blocks the wavelength range of light from 495 nm to 570 nm, the pilot 877 on the airplane or aircraft 870 is not affected by the green laser attack from the laser impactor 878 on the ground.
[0147] In some cases, the light control film (LCF) disclosed in the present invention can be used in combination with a retroreflector. For example, Fig.10A retroreflective system 1101 is shown, which includes a retroreflective sheet 1190 for retroreflecting light, and an LCF 1100 disposed on the retroreflective sheet 1190. Typically, the retroreflector sheet 1190 is configured to retroreflect light for a range of incident wavelengths and angles. For example, the retroreflector sheet 1190 can be configured to retroreflect light of different incident wavelengths λ1 and λ2 and different incident angles α and α'. Adding the LCF 1100 allows the system 1101 to have improved retroreflective properties. For example, for a larger angle α and a smaller angle α', the viewing angle 2θv of the LCF 1100 can be such that for a smaller incident angle α', the LCF 1100 substantially transmits light at both wavelengths λ1 and λ2, but for a larger incident angle α, the LCF can substantially transmit light having a wavelength λ1 and substantially absorb light having a wavelength λ2. For example, in some cases, the viewing angle θP of the LCF 1100 can be greater than α' and less than α. As another example, the retroreflective system 1101 is constructed as follows: for a first wavelength λ1, lights 810 and 810' are incident on the LCF 1100 at corresponding first and second incident angles α' and α, and are both retroreflected as corresponding retroreflected lights 812 and 812'. In addition, for a second wavelength λ2, light 820 incident on the LCF at the first incident angle α' is retroreflected as retroreflected light 822, but light 820' incident on the LCF at the second incident angle α is not retroreflected. In such cases, when light 820' is first incident on the LCF, and in some cases, after light 820' is partially transmitted by the LCF and retroreflected by the retroreflective sheeting, it is absorbed by the LCF 1100. In some cases, the LCF 1100 includes a larger first viewing angle for the first wavelength and a smaller viewing angle for the second wavelength. In some cases, first angle of incidence α' is substantially equal to zero with respect to line 801 normal to the plane of LCF 1100. In some cases, retroreflective sheeting 1190 includes microsphere beads 610 for retroreflecting light. In some cases, retroreflective sheeting 1190 includes cube corner cubes 620 for retroreflecting light. In some cases, LCF 1100 includes a plurality of spaced-apart first regions 1130, wherein each first region 1130 has a substantially low transmittance at a second wavelength λ2, but not at a first wavelength λ1.
[0148] In some cases, a light control film (LCF) can be used as part of an optical communication system with a sensor (more specifically, an IR sensor) to improve signal-to-noise performance and to improve direction sensing. In this example, the first material is spectrally selective in at least a portion of the infrared range, and in some cases, the second material can be spectrally selective in at least a portion of at least one of the ultraviolet and visible ranges. More desirably, the second material is spectrally selective in both the ultraviolet range and the infrared range. When using LCF, noise from the IR sensor, such as ultraviolet and visible light, is absorbed by the second material regardless of the incident angle of the light. Regardless of the incident angle of the light, the transmission of ultraviolet and visible light from the light source through the second region is uniform and desirably less than about 10%. However, the second region can transmit a range of infrared light from the light source, but the transmission of infrared light through the first region varies as a function of the incident angle of the light. When light is incident perpendicularly to the surface of the LCF, infrared light can be transmitted through the optical film. However, outside the viewing angle 2θv, infrared light is blocked by the first material in the first region. Thus, the disclosed system provides an IR sensor with significantly reduced noise and significantly improved directional sensing.
[0149] In another case, LCF can be used as part of an optical communication system with a sensor (more specifically, a pulse sensor for a wristwatch), such as Fig.11 shown. Specifically, Fig.11An exemplary application of an LCF applied to a wristwatch with a pulse sensor is shown. The LCF 1200 can be attached to a wearable wristwatch 1280 or any wearable device, and desirably attached to the surface of the wearable wristwatch 1280. The LCF 1200 includes an optical film 1250, which includes a plurality of first absorptive regions 1230 and an optional second (e.g., cover film) region 1240 adjacent to at least a portion of at least one of the first regions 1230. The first region 1230 includes a first absorptive material 1232, and the second region 1240 may include a second material 1242. The first material 1232 or the second material 1242 (e.g., cover film, adhesive, or coating) can be any suitable material such that the first material 1232 is spectrally selective in at least a portion of the visible light range from a light source (e.g., LED 1290), and the second material 1242 is spectrally selective in at least a portion of at least one of the ultraviolet light range and the infrared light range from the LED 1209. More desirably, the second material 1242 is spectrally selective in both the ultraviolet range and the infrared range. When the LCF 1200 is used, no matter what the incident angle of light from a light source such as sunlight 1295 or LED 1290 is, from the perspective of the pulse sensor 1285, noise such as ultraviolet light and infrared light are absorbed by the second material 1242. No matter what the incident angle of the light is, the transmission of ultraviolet light and infrared light from the light source through the second region 1240 is uniform and desirably less than about 10%. However, the second region 1240 transmits a range of visible light from the LED 1290, but the transmission of visible light through the first region 1230 varies as a function of the incident angle of the light. When the light from the LED 1290 is perpendicularly incident on the surface of the LCF 1200, the visible light can be transmitted through the optical film 1250. However, the first material 1232 can block or reduce sunlight 1295 or ambient visible light from other light sources that is incident on the wrist 777 of a person wearing the device at a relatively high angle of incidence, so that the LCF 1200 can improve the signal (primarily visible light from the LED that is incident within the viewing angle) to noise (e.g., ultraviolet light or infrared light, or ambient visible light from other ambient light sources such as sunlight that is incident outside the viewing angle) ratio.
[0150] This specification should not be considered limited to the specific examples described herein, but should be understood as covering all aspects of the specification clearly given in the attached claims. After reviewing this specification, various modifications, equivalent processes and numerous structures that can be applied to this specification will be apparent to those skilled in the art to which this specification relates. The above description can be better understood by considering the embodiments shown by experimental results and examples that follow.
[0151] Example
[0152] Unless otherwise specified, all parts, percentages, ratios, etc. in the examples and the rest of the specification are by weight. Unless otherwise specified, all chemicals were obtained or purchased from chemical suppliers such as Sigma-Aldrich Co., St. Louis, Missouri.
[0153] The following is a list of materials used throughout the examples, along with their brief descriptions and sources.
[0154] The compositions of Resin A used in the casting and curing microreplication process (Preparation Example 1) and the index matching backfill materials in Example 2 and Examples 4-8 are listed in Table 1 below. The raw materials used for layer-by-layer coating are listed in Table 2 below. The raw materials used for reactive ion etching are listed in Table 3 below.
[0155] Table 1: Raw materials used for resin A
[0156]
[0157] Table 2: Raw materials for layer-by-layer coating
[0158]
[0159] Table 3: Raw materials used for reactive ion etching
[0160]
[0161] Preparation Example 1 (PE1): Preparation of "square wave" microstructured film
[0162] A diamond (29.0 μm tip width, 3° included angle, 87 μm deep) was used to cut a tool with multiple parallel linear grooves. The grooves were spaced at a pitch of 62.6 microns.
[0163] Resin A was prepared by mixing the materials in Table 4 below.
[0164] Table 4: Composition of Resin A used to prepare microstructured films
[0165] Material Weight Photomer 6010 60 SR602 20 SR601 4.0 TMPTA 8.0 PEA (Etermer 2010) 8.0 Darocur 1173 0.35 TPO 0.10 I1035 0.20
[0166] The "cast and cure" microreplication process was performed with Resin A and tool as described above. Line conditions were: resin temperature 150°F, mold temperature 150°F, coater IR 120°F edge / 130°F center, tool temperature 100°F, and line speed 70 fpm. Fusion D lamps with a peak wavelength of 385 nm (available from Fusion UV Systems, Gaithersburg, MD.) were used for curing and operated at 100% power. The resulting microstructured film included a plurality of protrusions (e.g., light-transmitting areas) separated by channels, such as Figure 2 As shown. The base layer 260 is a PET film (3M, St. Paul, MN) having a thickness of 2.93 mils (74.4 microns). The side of the PET film that contacts the resin is primed with a thermosetting acrylic polymer (Rhoplex 3208, purchased from Dow Chemical, Midland, MI). The base layer (L) of the cured resin has a thickness of 8 microns. The microstructured film is a topological inversion of the tool, so that the protrusions of the microstructured film are a negative copy of the grooves of the tool. The protrusions have a wall angle of 1.5 degrees, resulting in a slight tapering of the protrusions (wider at the light input surface and narrower at the light output surface). The channels of the microstructured film are a negative copy of the uncut portion of the tool between the grooves.
[0167] Method for preparing layer-by-layer self-assembled coatings on microstructured films
[0168] The layer-by-layer self-assembled coatings were prepared using an apparatus purchased from Svaya Nanotechnologies, Inc. (Sunnyvale, CA) and according to US 8,234,998 (Krogman et al.) and Krogman et al. Automated process for improved uniformity and flexibility in layer-by-layer deposition , Langmuir, 2007, Vol. 23, pp. 3137-3141 (Krogman et al. Automated Process for Improved Uniformity and Versatility of Layer-by-Layer Deposition ,Langmuir 2007,23,3137-3141)) is used to model the system described in.
[0169] The apparatus includes a pressure vessel loaded with a coating solution. A spray nozzle with a flat spray pattern (purchased from Spraying Systems, Inc., Wheaton, Illinois) is installed to spray the coating solution and rinse water at a specified time controlled by a solenoid valve. The pressure vessel (Alloy Products Corp., Waukesha, WI) containing the coating solution is pressurized to 30 psi with nitrogen, while the pressure vessel containing deionized (DI) water is pressurized to 30 psi with air. The flow rate of the coating solution nozzle is 10 gallons per hour each, and the flow rate of the DI water rinse nozzle is 40 gallons per hour. The substrate to be coated was adhered at the edges to a glass plate (12" x 12" x 1 / 8" thick) (Brin Northwestern Glass, Minneapolis, MN) with epoxy (Scotch-Weld Epoxy Adhesive, DP100 Clear, 3M Company, St. Paul, MN). Co., Minneapolis, MN)), the glass plate is mounted on a vertical translation workbench and held in place with a vacuum chuck. In a typical coating sequence, a polycation (e.g., PDAC) solution is sprayed onto the substrate while the workbench moves vertically downward at 76 mm / s. Then, after a dwell time of 12 seconds, DI water is sprayed onto the substrate while the workbench moves vertically upward at 102 mm / s. The substrate is then dried with an air knife at a speed of 3 mm / s. Then, a polyanion (e.g., pigment nanoparticle) solution is sprayed onto the substrate while the workbench moves vertically downward at 76 mm / s. Another dwell time period of 12 s is allowed to pass. DI water is sprayed onto the substrate while the workbench moves vertically upward at 102 mm / s. Finally, the substrate is dried with an air knife at a speed of 3 mm / s. The above sequence is repeated to deposit a polycation / polyanion. n A plurality of "bilayers" of bilayers are prepared, where n is the number of bilayers. The coated substrate (eg, polymer film) is peeled off from the glass substrate and then subjected to subsequent processing.
[0170] Method for reactive ion etching of microstructured films
[0171] Reactive ion etching (RIE) was performed in a parallel plate capacitively coupled plasma reactor. The chamber had a surface area of 18.3 ft 2A central cylindrical powered electrode is placed on the powered electrode. After the microstructured film is placed on the powered electrode, the reaction chamber is pumped down to a base pressure of less than 1.3 Pa (2 mTorr). A mixture of Ar (argon) and O2 (oxygen) gases is flowed into the chamber, each at a rate of 100 SCCM. The treatment is carried out using a plasma enhanced CVD method by coupling RF power to the reactor at a frequency of 13.56 MHz and an applied power of 6000 watts. The treatment time is controlled by moving the microstructured film through the reaction zone. After treatment, the RF power and gas supply are stopped and the chamber is returned to atmospheric pressure. Additional information about materials, processes for applying cylindrical RIE, and additional details about the reactor used can be found in US8460568 B2.
[0172] Method for backfilling trenches in microstructured films
[0173] The channels were backfilled with Resin A used in PE1 by applying pressure to the top PET film using a hand roller to wick the resin between the microstructured film surface and a piece of unprimed 2 mil thick PET film placed on top, and then UV cured using a Heraeus (Hanau, Germany) belt conveyor UV processor (Model DRS (6)) and 'H' bulbs at 500 watts. Specifically, the sample was sent through the UV curing station three times at a conveyor speed of 50 ft / min. Next, the top PET film was peeled off the microstructured film by hand.
[0174] Method for measuring the brightness distribution of light from a diffuse light source
[0175] Film sample is placed on Lambertian light source.When light transmission area is conical, film is positioned so that the widest part of conical area is closer to light source.Use Eldim L80 conoscope (Eldim SA, HEROUVILLE SAINT CLAIR, France) to detect light output in a hemispherical manner at all polar angles and azimuth angles simultaneously.After detection, read the cross section of transmission (e.g., brightness) reading in the direction orthogonal to the direction of skylight (expressed as 0 ° orientation angle), unless otherwise specified.Relative transmittance (i.e., visible light brightness) is defined as the percentage of axial brightness at a specific viewing angle between the reading with film and the reading without film.
[0176] The Lambertian light source is from Figure 6The diffuse transmittance composition of the light box of the baseline light intensity distribution shown. The light box is a six-sided hollow prism measuring approximately 12.5 cm×12.5 cm×11.5 cm (L×W×H) and made of polytetrafluoroethylene (PTFE) diffuser sheet with a thickness of about 6 mm. One side of the box was selected as the sample surface. The diffuse reflectance at the sample surface of the hollow light box was measured to be about 0.83 (e.g., about 83% averaged over the wavelength range of 400 nm-700 nm). During the test, the box was illuminated from within the light box through a circular hole of about 1 cm located in the bottom of the box (opposite to the sample surface) (light was directed from the inside toward the sample surface). Illumination was provided using a stable broadband incandescent light source attached to a fiber optic bundle for directing light (Fostec DCR-II with a 1 cm diameter fiber optic bundle extension, from Schott-Fostec LLC, Marlborough Mass. and Auburn, NY).
[0177] Method for measuring the transmittance of ultraviolet and near infrared light
[0178] The transmittance of ultraviolet light (320 nm-400 nm) and near infrared light (700 nm-1400 nm) was measured using a Lambda 1050 spectrophotometer (Perkin Elmer, Waltham, Massachusetts) with a variable angle transmittance sample holder (Catalog No. PELA9042). The values reported in the examples are the arithmetic mean of the transmittance measured at a single location on each sample at the specified incident angle of +30° or +60° from 320 nm-400 nm (ultraviolet) or 700 nm-1400 nm (near infrared).
[0179] Methods for cross-sectional scanning electron microscopy (SEM)
[0180] Cross sections were prepared via freeze fracturing using liquid nitrogen. SEM images were acquired with a Hitachi SU-8230 (Hitachi, Ltd., Tokyo, Japan) instrument.
[0181] Comparative Examples 1-2 (CE1-CE2) are commercially available light control films.
[0182] Comparative Example 3 (CE3)
[0183] Two sections of film from CE1 (3"x3 each) were overlapped and laminated together with an optically clear adhesive (8171 from 3M Company, St. Paul, MN). One sheet was oriented perpendicular to the other. That is, the initial direction of the channels was offset 90° between the top sheet and the bottom sheet.
[0184] Preparation Example 2 (PE2): Preparation of coating solution
[0185] PDAC was diluted from 20 wt % to a concentration of 0.32 wt % with deionized (DI) water. PAA was diluted from 25 wt % to a concentration of 0.1 wt % and the pH was adjusted to 4.0 with 1 M NaOH. 200(COJ200), 250C(COJ250C), 260M(COJ260M) and 352K (COJ352K) was each diluted to a concentration of 0.10 wt%. NaCl was added to both the PDAC solution and the pigment suspension to a concentration of 0.05 M. 1 M NaOH was added to the COJ352K suspension to a pH of 9. pH values were measured using a VWR (West Chester, PA) pH electrode (Catalog No. 89231-582, which was calibrated with a standard buffer solution).
[0186] Preparation Example 3 (PE3): Preparation of Cationic Pigment
[0187] Polyethyleneimine (PEI) modified 352K (COJ352K) carbon black nanopigment (abbreviated as PEI-COJ352K). PEI (MW25K) was diluted to prepare a 10 wt% solution. 3.2 g of the 10 wt% PEI solution was diluted to 794.7 g with DI water. Then, 5.3 g of COJ352K with a solid content of 15.03% was added dropwise to 794.7 g of the PEI solution under vigorous magnetic stirring to produce a final concentration of 0.1 wt% COJ352K and 0.04 wt% PEI. The polyethyleneimine (PEI) modified carbon nanopigment was measured using a ZetaPALS instrument from Brookhaven Instruments Corp. (Holtsville, NY) with an aliquot of the PEI-COJ352K sample diluted 100 times with 1 mM KCl as described above. Size and zeta potential of 352K (COJ352K). Particle size is determined by d 10 =77.5nm, d50 =148.4nm and d 90 =284.0nm. Zeta potential was measured to be +37.9mV±0.9mV.
[0188] Example 1 (EX1): Carbon black nanopigment, 130 nm diameter, no backfill
[0189] The microstructured film sheets prepared in PE1 were cut into 9" x 10" dimensions and corona treated by hand using a BD-20AC laboratory corona treater (Electro-Technic Products, Chicago, IL) to prevent beading and dewetting of the aqueous coating solution. PDAC and 200 coating solution. Use "Method for preparing spray-coated layer-by-layer self-assembled coating on microstructured film" with (PDAC / COJ200) 10 The film treated with corona was coated. The coated film was subjected to reactive ion etching (RIE) at a power of 6000 W for a duration of 210 s. After scratching the coating with a razor blade, the thickness of the equivalent coating deposited on the glass plate measured with a Dektak XT stylus profiler (Bruker Nano, Inc., Tucson, AZ) was 166 nm. Based on the thickness of the equivalent coating deposited on the glass, the aspect ratio of the absorbing region (e.g., skylight) was approximately 525:1.
[0190] Example 2 (EX2): Carbon black nanopigment, 130 nm diameter, backfilled
[0191] The microstructured film sheets prepared in PE1 were cut into 9" x 10" dimensions and corona treated by hand using a BD-20AC laboratory corona treater (Electro-Technic Products, Chicago, IL) to prevent beading and dewetting of the aqueous coating solution. PDAC and 200 coating solution. Use "Method for preparing spray-coated layer-by-layer self-assembled coating on microstructured film" with (PDAC / COJ200) 20 The corona treated film was coated. The coated film was subjected to reactive ion etching (RIE) at a power of 6000 W for a duration of 210 s. Next, the trenches were backfilled using the "Method for Backfilling the Trench of a Microstructured Film" described above. After scratching the coating with a razor blade, the thickness of the equivalent coating deposited on a glass plate was measured with a Dektak XT stylus profilometer to be 326 nm.
[0192] Example 3 (EX3): Carbon black nanopigment, 70nm-80nm diameter, no backfill
[0193] The microstructured film sheets prepared in PE1 were cut into 9" x 10" dimensions and corona treated by hand using a BD-20AC laboratory corona treater (Electro-Technic Products, Chicago, IL) to prevent beading and dewetting of the aqueous coating solution. PDAC and 352K coating solution. Use "Method for preparing spray-coated layer-by-layer self-assembled coatings on microstructured films" with (PDAC / COJ352K) 20 The corona treated film was coated with 1000 W of 1% CO 2 . The coated film was then subjected to reactive ion etching (RIE) for a duration of 200 s at a power of 6000 W. The thickness of the equivalent coating deposited on a glass plate was measured to be 273 nm with a Dektak XT stylus profilometer after scratching the coating with a razor blade.
[0194] Example 4-6 (EX4-6): Carbon black nanopigment, 70nm-80nm diameter, backfilled
[0195] Each of the three microstructured membrane sheets prepared in PE1 was cut into 9" x 10" dimensions and corona treated by hand using a BD-20AC laboratory corona treater (Electro-Technic Products, Chicago, IL) to prevent beading and dewetting of the aqueous coating solution. PDAC and 352K coating solution. Use "Method for preparing spray-coated layer-by-layer self-assembled coatings on microstructured films" with (PDAC / COJ352K) 20 (EX4), (PDAC / COJ352K) 40 (EX5) and (PDAC / COJ352K) 60 (EX6) was used to coat a separate 9" x 10" piece of the corona treated film. The coated film was subjected to reactive ion etching (RIE) at a power of 6000 W for a duration of 200 s (EX4) and 500 s (EX5 and EX6). Cross-sectional SEM images of EX4 were obtained before and after RIE but before backfilling. It is apparent from the SEM images that the coating deposited on the film has a uniform thickness and that the thickness corresponds to an equivalent coating deposited on glass, as described below. Next, the trenches were backfilled using the "Method for Backfilling Trenches in Microstructured Films" described above. The brightness distribution of light from a diffuse light source was measured using the "Method for Measuring Brightness Distribution from a Diffuse Light Source" described above ( Figure 6 and the data in Tables 5A and 5B). The thickness of the equivalent coatings deposited onto the glass plates after scratching with a razor blade was measured with a Dektak XT stylus profilometer to be 273 nm (EX4), 536 nm (EX5), and 796 nm (EX6). Based on the thickness of the equivalent coatings deposited on the glass, the aspect ratios of the absorbing regions (e.g., skylights) ranged from approximately 109:1 (for EX6) to 319:1 (for EX4).
[0196] Table 5A: Relative brightness (RB) of EX2, EX4-EX6 and CE1-CE2.
[0197]
[0198] Table 5B: Relative brightness (RB) of EX2, EX4-EX6 and CE1-CE2.
[0199]
[0200] Table 5C: Transmittance of UV and NIR light of EX6
[0201]
[0202] Example 7 (EX7): Overlapping, intersecting membranes
[0203] Two portions (3" x 3 each) of a light control film prepared according to EX4 were overlapped with the structured sides facing each other and one sheet oriented perpendicular to the other. That is, the initial direction of the channels was offset 90° between the top sheet and the bottom sheet. Resin A was dispensed between the two sheets and the two sheets were laminated together with a hand roller. The samples were cured as described in the "Method for Backfilling Channels of Microstructured Films" and measured using the "Method for Measuring Brightness Distribution of Light from a Diffuse Light Source". The data are shown in Tables 6A and 6B.
[0204] Example 8 (EX8): Overlapping, aligned membranes
[0205] Two portions (3" x 3 each) of a light control film prepared according to EX4 were overlapped with the structured sides facing each other and one sheet oriented parallel to the other. That is, the initial direction of the channels was aligned between the top sheet and the bottom sheet. Resin A was dispensed between the two sheets and the two sheets were laminated together with a hand roller. The samples were cured as described in the "Method for Backfilling Channels of Microstructured Films" and measured using the "Method for Measuring Brightness Distribution of Light from a Diffuse Light Source". The data are shown in Tables 6A-6D.
[0206] Table 6A: Relative brightness measured for EX7-EX8 and CE3 .
[0207]
[0208] Table 6B: Relative brightness measured for EX7-EX8 and CE3 .
[0209]
[0210] Table 6C: Relative brightness measured at 90° orientation angle for EX7-EX8 and CE3 .
[0211]
[0212] Table 6D: Relative brightness measured at 90° orientation angle for EX7-EX8 and CE3 .
[0213]
[0214] Example 9A (EX9A): Cyan nanopigment coating, no backfill
[0215] The microstructured film sheets prepared in PE1 were cut into 9" x 10" dimensions and corona treated by hand using a BD-20AC laboratory corona treater (Electro-Technic Products, Chicago, IL) to prevent beading and dewetting of the aqueous coating solution. PDAC and 250C coating solution. Use "Method for preparing spray-coated layer-by-layer self-assembled coating on microstructured film" with (PDAC / COJ250C) 20 The film treated with corona was coated. The coated film was subjected to reactive ion etching (RIE) at a power of 6000 W for a duration of 150 s. The relative brightness was measured using the "method for measuring the distribution of light brightness from a diffuse light source" (data in Table 7). After scratching the coating with a razor blade, the thickness of the equivalent coating deposited on the glass plate measured by a Dektak XT stylus profiler (Bruker Nano, Inc., Tucson, AZ) was 340 nm.
[0216] Example 9B (EX9B): Cyan nanopigment coating, backfilled
[0217] The microstructured film was prepared as described in 9A, except that the trenches were backfilled using the "Method for Backfilling the Trench of a Microstructured Film" described above. The relative brightness was measured using the "Method for Measuring the Brightness Distribution of Light from a Diffuse Light Source" (data in Table 7). The thickness of the equivalent coating deposited on a glass plate was 340 nm as measured by a Dektak XT stylus profilometer (Bruker Nano, Inc., Tucson, AZ) after scratching the coating with a razor blade.
[0218] Example 10A (EX10A): Magenta Nanopigment Coating, No Backfill
[0219] The microstructured film sheets prepared in PE1 were cut into 9" x 10" dimensions and corona treated by hand using a BD-20AC laboratory corona treater (Electro-Technic Products, Chicago, IL) to prevent beading and dewetting of the aqueous coating solution. PDAC and 260M coating solution. Use "Method for preparing spray-coated layer-by-layer self-assembled coating on microstructured film" with (PDAC / COJ260M) 20 The film treated with corona was coated. The coated film was subjected to reactive ion etching (RIE) at a power of 6000 W for a duration of 150 s. The relative brightness was measured using the "method for measuring the distribution of light brightness from a diffuse light source" (data in Table 7). After scratching the coating with a razor blade, the thickness of the equivalent coating deposited on the glass plate measured by a Dektak XT stylus profiler (Bruker Nano, Inc., Tucson, AZ) was 313 nm.
[0220] Example 10B (EX10B): Magenta nano-pigment coating, backfilled
[0221] The microstructured film was prepared as described in 10A, except that the trenches were backfilled using the "Method for Backfilling the Trench of a Microstructured Film" described above. The relative brightness was measured using the "Method for Measuring the Brightness Distribution of Light from a Diffuse Light Source" (data in Table 7). The thickness of the equivalent coating deposited on a glass plate was 313 nm as measured by a Dektak XT stylus profilometer (Bruker Nano, Inc., Tucson, AZ) after scratching the coating with a razor blade.
[0222] Table 7A: Relative brightness of EX9-EX10
[0223]
[0224] Table 7B: Relative brightness of EX9-EX10
[0225]
[0226] Table 7C: UV and NIR Transmittance of EX9A-EX10B
[0227]
[0228] Example 11 (EX 11): Cationic pigment, anionic polymer electrolyte
[0229] Glass microscope slides (Fisher Scientific, Waltham, MA) measuring 1" x 3" were rinsed with DI water and isopropanol. The slides were mounted on a StratoSequence VI (nanoStrata, Inc., Tallahassee, FL) automated layer-by-layer dip coater. The slides were immersed in the PEI-COJ352K solution described in PE3 for 1 minute. Next, the slides were immersed in three consecutive DI water rinse baths for 30 seconds each. Next, the slides were immersed in a PAA solution (0.1 wt %, adjusted to pH 4 with HCl) for 1 minute. Next, the slides were immersed in three consecutive DI water rinse baths for 30 seconds each. The slides were rotated at 150 rpm in each bath. This cycle was repeated a total of 10 times to deposit (PEI-COJ352K / PAA) 10 The thickness of the coating was 4 μm as measured with a Dektak XT stylus profilometer (Bruker Nano, Inc., Tucson, AZ) after scratching the coating with a razor blade. A microstructured film of PE1 can be coated layer by layer with the composition and subjected to RIE as previously described.
[0230] Example 12 (EX 12): Cationic pigment, anionic pigment
[0231] Glass microscope slides (Fisher Scientific, Waltham, MA) measuring 1" x 3" were rinsed with DI water and isopropanol. The slides were mounted on a StratoSequence VI (nanoStrata, Inc., Tallahassee, FL) automated layer-by-layer dip coater. The slides were immersed in a PEI-COJ352K solution (as described in PE3) for 1 minute. Next, the slides were immersed in three consecutive DI water rinse baths for 30 seconds each. Next, the slides were immersed in a COJ352K solution (as described in PE2) for 1 minute. Next, the slides were immersed in three consecutive DI water rinse baths for 30 seconds each. The slides were rotated at 150 rpm in each bath. This cycle was repeated a total of 10 times to deposit (PEI-COJ352K / COJ352K) 10The thickness of the coating was 240 nm as measured with a Dektak XT stylus profilometer (Bruker Nano, Inc., Tucson, AZ) after scratching the coating with a razor blade. A microstructured film of PE1 can be coated layer by layer with the composition and subjected to RIE as previously described.
[0232] Example 13 (EX 13):
[0233] As in EX. 1. During the process of backfilling the channels of the microstructured film, the top PET film was replaced with a color shifting film as described in Example 1 of WO 2010 / 1090924. After UV curing, the color shifting film was not peeled off but remained as a cover film.
[0234] Table 8A: Relative brightness of EX13
[0235]
[0236] The highly reflective color shifting film causes light recycling in the gain prism, resulting in an axial relative brightness greater than 100%.
[0237] Table 8B: Transmittance of UV and NIR of EX13
[0238]
[0239] Surface area of the absorption zone
[0240] The light input surface of CE2 was observed with an optical microscope at 200× magnification. The maximum widths of the various absorption regions (i.e., Figure 1a W A ) and spacing (i.e., Figure 1a P A ). The average width of the five absorbing regions was measured to be 14.7 microns. The average spacing was measured to be 64.9 microns. Therefore, the ratio W A / P A This is equal to 0.227 or 22.7% of the surface area.
[0241] The light input surface of EX6 was observed with an optical microscope at 200 times magnification. The maximum widths of the multiple absorption regions (i.e., Figure 1a W A ) and spacing (i.e., Figure 1a P A ). The average width of the five absorbing regions was measured to be 1.0 micrometer. The average spacing was measured to be 31.2 micrometers. When the wall angle is zero, the ratio W A / P A This is equal to 0.032 or 3.2% of the surface area. For a 1.5 degree wall angle, the surface area is 10.8%.
[0242] The embodiments 1-13 just described may be modified to include in at least one of the following: a light-absorbing layer (e.g., a cover film, a base layer, an adhesive, a coating) or a light-reflecting layer (e.g., a diffuser layer) located between the alternating transmissive regions and absorptive regions and the light output surface or the light input surface, or a light-absorbing material that can be added to the material of the light-transmissive region.
[0243] Comparative Example 4 (CE4)
[0244] A dyed polyester film was prepared according to Example 1 of US 9,630,384, except that the thickness was 1.5 mils (38 micrometers) as measured with Haze-Gard Plus (BYK-Gardner USA, Columbia, Maryland) to achieve a visible light transmission level of 7%. A 3" x 3" section of the dyed polyester top film was laminated to a 3" x 3" piece of commercial privacy / light management film using a hand roller with an optically clear adhesive (8171, available from 3M Company, St. Paul, MN).
[0245] Example 14 (EX 14): LCF with PET cover film including light absorbing dye
[0246] The microstructured films prepared in PE1 were each cut into 9" x 10" dimensions and corona treated by hand using a BD-20AC laboratory corona treater (Electro-Technic Products, Chicago, IL). PDAC and 352K coating solution. Use the "Method for preparing layer-by-layer self-assembled coatings on microstructured films" to (PDAC / COJ352K) 60 The coating was deposited onto the film. The thickness of the equivalent layer-by-layer coating deposited onto the glass plate was 796 nm as measured by a Dektak XT stylus profilometer after scratching the coating with a razor blade. The coated film was subjected to reactive ion etching (RIE) at a power of 6000 W for a duration of 500 s. Next, the trenches were backfilled using the "Method for Backfilling the Trench of a Microstructured Film" described above to prepare a light control film.
[0247] A 3" x 3" section of the dyed polyester film of CE4 was laminated to a 3" x 3" piece of light management film using an optically clear adhesive (8171, available from 3M Company, St. Paul, MN). Light transmittance was measured as described above. The results are as follows:
[0248] Inclusion of the LCF increased the transmittance at normal incidence (0 degree viewing angle) by 14% and decreased the UV and NIR transmittance at 30° and 60° viewing angles.
[0249] Table 9A: Relative brightness of EX14 and CE4
[0250]
[0251] Table 9B: Relative brightness of EX14 and CE4
[0252]
[0253] Table 9C: Ultraviolet (UVA) and near-infrared light transmittance of EX14 and CE4
[0254]
[0255] PE4 – Preparation of adhesive
[0256] The base adhesive formulation was prepared as follows. 40 g of 2-ethylhexyl acrylate (Sigma-Aldrich, St. Louis, MO), 40 g of n-butyl acrylate (BASF Florham Park, NJ), 15 g of 2-hydroxyethyl acrylate (Kowa America New York, NY), 5 g of acrylamide (Zibo Xinye Chemical, Zibo City, CN), 0.08 g of thermal initiator Vazo52 (Dupont (Wilmington, DE)), 0.08 g of Karenz MT PE1 (Showa Denko America, New York, NY), and 60 g of methyl ethyl ketone (MEK) solvent were charged to a reactor vessel. The container was sprayed with nitrogen for 5 minutes, sealed, and then placed in a stirred water bath at 60°C for 20 hours. The resulting solution polymer was then cooled, sprayed with air for 10 minutes, and 0.3 g of isocyanatoethyl methacrylate (IEM purchased from Showa Denko America, New York, NY) was added to the container. The container was sealed again and heated to 50°C for 12 hours to allow the IEM to react with the pendant OH functional groups on the acrylic polymer formed. After the functionalization, 0.4 g of Irgacure-184 (BASF Florham Park, NJ) and 8 g of CN983 (Sartomer, Exton, PA) were added to the container and mixed for 1 hour.
[0257] Example 15 (EX15)
[0258] Orasol Red 395 (BASF) was dissolved in MEK at 10 wt%. One dye solution was mixed with 2 parts of PE4 adhesive to form a coating solution containing 3.33 wt% of Orasol red 395 dye. The coating solution was applied to the primer side of a PET film (the same PET film used in PE-1) using a No. 28 Meyer rod (RDS Specialties, Webster, York, New York) and dried in an oven at 150°F for 6 minutes. A PET film with a colored adhesive layer (23 microns) was laminated to a light control film as described in EX2 using a Catena 65 roll laminator (purchased from GBC, Lake Zurich, IL) at a speed of 5 feet per minute and a gap of 1 mm. The film was presented as red coaxial and black off-axis.
[0259] Example 16 (EX16)
[0260] Orasol Blue 825 (BASF) was dissolved in MEK at 10 wt%. One dye solution was mixed with 2 parts of PE4 adhesive to form a coating solution containing 3.33 wt% of Orasol Blue 825 dye. The coating solution was applied to PET and laminated to a film from EX2 as described above in EX17. The film appeared blue on-axis and black off-axis.
[0261] The light transmittance of EX15 and EX16 was measured as described above. The results are as follows:
[0262] Table 10A: Relative brightness of EX15-EX16
[0263]
[0264] Table 10B: Ultraviolet (UVA) and near-infrared transmittance of EX15-EX16
[0265]
Claims
1. A light control film, comprising: a light input surface and a light output surface opposite to the light input surface; alternating transmissive and absorptive regions disposed between the light input surface and the light output surface, wherein the absorptive regions have an aspect ratio of at least 100, the aspect ratio being defined as the ratio of the height of the absorptive regions divided by the maximum width of the absorptive regions, the absorptive regions having an average width no greater than 5 microns, and the absorptive regions comprising a polymer electrolyte and a light absorbing material ionically bonded to the polymer electrolyte; as well as An absorbing layer or a reflecting layer is disposed between the alternating transmissive and absorptive regions and the light input surface and / or the light output surface, provided that the reflecting layer is not a wavelength shifting film. 2 . The light control film of claim 1 , wherein the absorbing layer comprises a pigment and / or a dye.
3. The light control film of claim 1 or 2, wherein the absorptive layer comprises an adhesive or a coating disposed between the alternating transmissive and absorptive regions and the light output surface or the light input surface.
4. The light management film of claim 3 further comprising a cover film such that the adhesive or coating is located between the cover film and the alternating transmissive and absorptive regions.
5. The light management film of claim 1 or 2, wherein the absorptive layer comprises a film layer disposed between the alternating transmissive and absorptive regions and the light input surface or the light output surface. The light control film of claim 5 , wherein the film layer is a cover film or a substrate layer.
7. The light control film of any one of claims 1 to 2, wherein the alternating transmissive and absorptive regions have a relative transmission of at least 75% as measured with a conoscope at a viewing angle of 0 degrees for a wavelength range of 400 nm to 700 nm.
8. The light control film of any one of claims 1 to 2, wherein the alternating transmissive and absorptive regions have a transmittance of less than 50%, 45%, 40% or 30% as measured spectrophotometrically at a viewing angle of 0 degrees for wavelengths in the range of 320 nm-400 nm (UV).
9. The light control film of any one of claims 1 to 2, wherein the alternating transmissive and absorptive regions have a transmittance of at least 65%, 70%, 75% or 80% as measured spectrophotometrically at a viewing angle of 0 degrees for wavelengths in the range of 700 nm to 1400 nm (NIR).
10. The light control film of claim 1, wherein the absorptive region has a width parallel to the light input surface and a height normal to the light input surface, and the height is greater than the width.
11. The light control film of any of claims 1, 2, and 10, wherein the alternating transmissive and absorptive regions have a relative transmittance for visible light of less than 50%, 45%, 40%, 35%, 30%, 25%, 20%, 10%, or 5% at a viewing angle of +30 or -30 degrees.
12. The light control film of any one of claims 1, 2, and 10, wherein the alternating transmissive and absorptive regions have an average relative transmittance of less than 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, or 2% for visible light at a viewing angle of +35 to +80 degrees, or an average relative transmittance of less than 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, or 2% for visible light at a viewing angle of -35 to -80 degrees.
13. The light control film of any of claims 1, 2, and 10, wherein the transmissive regions have a wall angle of less than 5 degrees, 4 degrees, 3 degrees, 2 degrees, 1 degree, or 0.1 degrees.
14. The light control film of any of claims 1, 2, and 10, wherein the transmissive regions and the absorptive regions have a height in a range of 50 microns to 200 microns.
15. The light management film of any of claims 1, 2, and 10, wherein the absorptive regions have an average width of no greater than 4 microns, 3 microns, 2 microns, 1 micron, 0.5 microns, 0.25 microns, or 0.10 microns.
16. The light control film of any of claims 1, 2, and 10, wherein the absorptive regions have an aspect ratio of at least 200, 300, 400, 500, 600, 700, 800, or 1000.
17. The light management film of any of claims 1, 2, and 10, wherein the absorptive regions have an average spacing of 10 microns to 200 microns.
18. The light control film of any of claims 1, 2, and 10, wherein the transmissive regions have an aspect ratio of at least 2, 3, 4, 5, 6, 7, 8, 9, or 10.
19. The light management film of any one of claims 1, 2, and 10, wherein the absorptive regions comprise an organic light absorbing material.
20. The light management film of any of claims 1, 2, and 10, wherein the absorptive regions comprise light absorbing particles having a median particle size of less than 500 nanometers.
21. The light management film of any one of claims 1, 2, and 10, wherein the absorptive region comprises at least 25 weight percent light absorbing particles.
22. The light control film of any of claims 1, 2, and 10, wherein the transmissive regions comprise a radiation cured (meth)acrylate polymer.
23. The light control film of any one of claims 1, 2, and 10, wherein the light control film has a relative transmittance of less than 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10% at a viewing angle of 0 degrees for a wavelength range of 400 nm to 700 nm as measured by conoscope.
24. The light management film of any one of claims 1, 2, and 10, wherein the light management film has a relative transmission of at least 75% at a viewing angle of 0 degrees for a wavelength range of 400 nm to 700 nm as measured with a conoscope.
25. The light management film of any of claims 1, 2, and 10, wherein the light management film has a transmittance of at least 60%, 65%, 70%, 75%, or 80% at a 0 degree viewing angle for wavelengths in the range of 700 nm-1400 nm (NIR).
26. The light control film of any one of claims 1, 2, and 10, wherein the light control film has an average transmittance of less than 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, 5%, 4%, 3%, 2%, or 1% for a wavelength range of 700 nm-1400 nm (NIR) at a viewing angle of 30 degrees.
27. The light control film of any one of claims 1, 2, and 10, wherein the light control film has an average transmittance of less than 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, 5%, 4%, 3%, 2%, or 1% for a wavelength range of 700 nm-1400 nm (NIR) at a 60 degree viewing angle.
28. The light control film of any one of claims 1, 2, and 10, wherein the absorptive regions block light over a maximum surface area at the light input surface or the light output surface, and the maximum surface area is less than 20% of the total surface area of the alternating transmissive and absorptive regions.
Citation Information
Patent Citations
Method of Asymmetrically Functionalizing Porous Materials
US20110064936A1
Methods and apparatus for embossing a precision optical pattern in a resinous sheet or laminate
US4601861A
Birefringent interference polarizer
US5486949A
Birefringent interference polarizer
US5612820A
Method for making an optical film
US5783120A